High-resolution carbon isotope chemostratigraphy of the upper Cambrian from the East Tarim Basin and implications for global correlation and paleoenvironment reconstruction - Xiao-Jun Zuo; Bo Chen; Hong-Xing Wei; Zhi-Xin Sun; Xin-Sheng Luo; Guo-Xiang Li; Zhi-Bin Huang; Miao Lu; Yong-Quan Chen; Ai-Hua Yang; Fang-Chen Zhao; Mao-Yan Zhu (Palaeoworld, 2026)

Unsupervised learning driven graded monitoring diagnosis of bridge tension-compression bearing degradation - Jia-Zheng Sun; Dong-Hui Yang; Ting-Hua Yi; Hai-Xin Du; Yong-Bo Li (Engineering Structures, 2026)

Efficient purification of bio-oil-derived levoglucosenone via a multi-stage synergistic separation strategy - Kai Li; Yong-sheng Ma; Bo Wang; Ding-wang Qiao; Qi Niu; Cheng-long Ruan; Bi-heng Bao; Xin-hua Yuan; Qiang Lu (Biomass and Bioenergy, 2026)

A salt-tolerant dual-network hydrogel based on tea waste biochar for efficient seawater desalination - Kun-Xiu Liu; Yi-Bin Li; Lei Xu; Cai-Hua Liu; Zhu-Long Yu; Wen-Bo Guo; Ming-Lai Fu; Baoling Yuan (Journal of Environmental Chemical Engineering, 2026)

Eco-hydrological processes in controlling vertical and lateral carbon fluxes in a subtropical salt marsh: Insights from modeling and scale-resolved analysis - Ke-Hua Zhu; Li-Shan Tan; Guan-Xun Wang; Li-Ming Xue; Zeng-Feng Li; Hua-Yu Chen; Qing Lyu; Bo-Fei Li; Wei Zhao; Christian Schwarz; Zhen-Ming Ge (CATENA, 2026)

Protein network on reticular heterostructure for competitive organic photoelectrochemical transistor biosensing - Bo-Han Kou; Peiying Yin; Miao-Hua Chen; Hai-Yan Wang; Zheng Li; Wei-Wei Zhao; Jing-Juan Xu (Analytica Chimica Acta, 2026)

Sedimentary-diagenetic characteristics and genesis of the Upper Cambrian reservoirs in the Tabei area, Tarim Basin, NW China - Jun Li; Kaibo Shi; Bo Liu; Yongsheng Ma; Yuanchong Wang; Qing He; Jiaming Deng; Xichuan Men; Xiangyu Bai; Jianhao Hua (Journal of Asian Earth Sciences, 2026)

“Precursors-in-action” nanoreactor: Coordination-activated self-assembly of cu/Fe bimetallic multifunctional metalloenzyme mimics for cascade-amplified breast cancer therapy - Peng Wang; Xin-Yi Zhang; Ying-Ying Han; Zhi-Yuan Li; Qing-Hua Shen; Long-Bo Yu; Cai-Ping Tan (Chemical Engineering Journal, 2026)

Polystyrene microplastics induce auditory neurotoxicity in mammals: Integrated multi-omics profiling reveals oxidative damage and synaptic molecular dysregulation - Huanzhi Wan; Jingchun Liu; Xuan Yu; Ting Li; Wenting Yu; Bo Liu; Yingzhao Liu; Yuanyuan Zhang; Shimin Zong; Qingquan Hua; Hongjun Xiao (Journal of Hazardous Materials, 2026)

Mesozoic continental crustal growth: A comprehensive review of the accretion-arc system in the Jilin-Heilongjiang high-pressure belt - Zhong-Hua Xin; Jian-Bo Zhou; Wen-Jiao Xiao; Jiang-Tao Han; Gong-Yu Li; Xiao-Miao Tan; Hong-Da Liang; Zhuo Chen; Hong-Yan Wang; Ning-Chen Sun; Rui Gao (Earth-Science Reviews, 2026)

Comprehensive epigenetic landscape of Sulfur Mustard (SM) exposure in HaCaT keratinocytes - Yuejia Du; Bo Ma; Yuanjie Li; Yanli Zhu; Zhi Li; Minmin Qu; Qinyun Shi; Weiwei He; Jia Chen; Bin Xu; Jie Li; Wenqi Meng; et al. (Chemico-Biological Interactions, 2026)

Wild Tibetan macaques employ a social sleep strategy to balance sleep needs and ecological pressures - Pei-pei Yang; Pritish Chakravarty; Wen-bo Li; Zi-tan Song; Xi Wang; Margaret C. Crofoot; Jin-hua Li (Animal Behaviour, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Axial compressive behavior of double-skin stainless steel tube columns filled with High-Strength Engineered Cementitious Composites (HS-ECC) - Wei-Chen Wang; Yu-Xuan Zheng; Jia-Qi Zhou; Jun-Hua Li; Ke-Xin Weng; Yi-Nong Shen; Bo-Tao Huang (Ocean Engineering, 2026)

Valorization of desulfurization sulfur paste for enhanced mixotrophic denitrification in a stratified fluidized-bed bioreactor - Wei-Zhe Chen; Tian-Hu Chen; Ya-Qian Li; Xue-Hua Zou; Hai-Bo Liu; Yue-Fei Zhou (Journal of Environmental Chemical Engineering, 2026)

Zeolite-assisted Ga0.8V0.2Ox oxygen carriers boost propane dehydrogenation via chemical looping - Bo Chen; Yuhao Wang; Ping Jin; Hua Wang; Kongzhai Li; Aimin Zhang; Yane Zheng (Fuel, 2026)

Differential volatile-omics analysis for tamarind (Tamarindus indica L.) and aroma-active compounds identification via DMU-SPME-GC-MS method - Rui-Hua Jin; Ling Zhang; Li-Bo Qi; Chun-Mei Yuan; Zi-Bo Song; Jia-Teng Chen; Ming Du; Xian-Bing Xu (Food Chemistry, 2026)

Freeze-thaw-damaged steel-reinforced concrete columns strengthened with High-Strength Engineered Cementitious Composites (HS-ECC) - Wei-Chen Wang; Yi-Nong Shen; Jun-Hua Li; Bo-Tao Huang (Engineering Structures, 2026)

Diagnosis of neurodegenerative diseases based on molecular imaging - Li Quan; Maoran Lang; Jiangtao Yue; Jiatao Zhu; Jinyao Xu; Kewei Wang; Hao Huang; Qinyong Song; Yingshi Zhao; Zhu Zhu; Chenqi Zhu; Bo Liu; et al. (Chemical Engineering Journal, 2026)

MXene-enhanced self-healing nanocomposite hydrogels with multiple-dynamic-bond crosslinking for motion sensing and information transmission - Ze-Hua Hou; Huan-Jie Che; Zi-Han Jiang; Xing Wu; Jin-Ping Yuan; Jing Li; Jian-Bo Qu (Chemical Engineering Journal, 2026)

N-doping strategy and peripheral substituent engineering enable Indolo[3,2,1-jk]carbazole harvesting multi-resonance TADF feature with deep-blue narrowband emission - Yi Chen; BoHua Zhang; YangYi Li; JiangXue Pei; QingYu Jia; ChaoBo Hao; WanQin Wang; Hua Dong; Bo Jiao; ZhaoXin Wu; HaiCheng Wei; GuiJiang Zhou; et al. (Chemical Engineering Journal, 2026)

Retraction Note: Role of Glibenclamide in Brain Injury After Intracerebral Hemorrhage - Bing Jiang; Lin Li; Qianwei Chen; Yihao Tao; Liming Yang; Bo Zhang; John H. Zhang; Hua Feng; Zhi Chen; Jun Tang; Gang Zhu (Translational Stroke Research, 2026)

Histamine regulation in shaping spindle refractoriness: a computational modeling study - Bo Wang; Qiang Li; Wen-Hua Wang; Wan-Rong Zan; Yi-Ming Li; Jiang-Ling Song; Rui Zhang (Journal of Computational Neuroscience, 2026)

The phase and energy-level evolutions in seven distinct sequential states and their hierarchical memory effect of isomeric MOFs - Rui-Fang Ma; Jia-Xin Wu; Ming-Zhu Chen; Tao Liu; Jian Li; Yi-Bo Zhang; Lei Shi; Sheng Liao; Fei Gao; Yi-Hang Guo; Yingbo Zhao; Zheng Yin; et al. (Science Bulletin, 2026)

Toward high-precision, low-consumption bulk analysis: advancements in extraterrestrial sample studies - Ding-Shuai Xue; Shun Guo; Yan-Hong Liu; Dan-Ping Zhang; Yong-Gang Yao; Bo Wan; Xian-Hua Li (Science Bulletin, 2026)

A new pathway to enhance the oceanic carbon sink: inorganic carbonate precipitation driven by calcium–alkali coupling - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Lei Li; Bao Xiao Qu; Qi Dong Wang; Jun Ma; Jian Wei Xing; Zhi Bo Wang; Rui Wang; et al. (Journal of Environmental Management, 2026)

Artificial grassland establishment alters soil metabolomes by reshaping multi-domain microbial networks - Bo Wang; Chao Peng; Hua Li; Zhuo Duan; Jianan Li; Xue Yang; Xiaoyun Wang; Tao Wang; Chuangxin Wang; Jiande Li; Wenliang Li; Guoying Zhou (Journal of Environmental Management, 2026)

Deciphering the molecular regulatory mechanism underlying behavioral disorders and cardiac damage in Eriocheir sinensis under saline-alkaline environment - Meiyao Wang; Pao Xu; Jianlin Li; Guoan Hua; Bo Peng; Yuqing Wu; Jun Zhou; Yongkai Tang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

In situ SIMS Pb-Pb dating of aeschynite reveals Early Paleozoic Nb mineralization at Bayan Obo - Bo Yang; Li Yang; Zhao Yan; Qing Sun; Yu Liu; Xiao-Xiao Ling; Xin-Yu Hou; Yong-Gang Zhao; Guo-Ying Yan; Jian-Yong Liu; Xian-Hua Li (Science Bulletin, 2026)

Chemical constituents from the stem of Nauclea officinalis and their anti-inflammatory activities - Bo Wen Wan; Ting Wang; Xiong Bo Zhu; Rui Hua Xu; Hao Fu Dai; Wen Li Mei; Fei Wu; Xiao Ying Peng; Sheng Zhuo Huang (Phytochemistry Letters, 2026)

Enhanced wastewater treatment performance in a two-stage pyrite-based denitrifying deep bed filter - Jun Ding; Feng Ling; Shu-Yang Tian; Wen-Bo Xie; Xiao-Cai Chen; Li Yu; Xu-Mei Li; Fa-Zhi Xie; Wei-Hua Li; Tong-Zhan Xue; Hou-Yun Yang; Xian-Huai Huang (Journal of Environmental Chemical Engineering, 2026)

Construction and Application of Traditional Chinese Medicine Knowledge Graph Based on Large Language Model - Bo Zhang; Ruifang Li; Kedong Yin; Shuo Hua; Shiyu Li; Mengwan Jiang; Haoping An; Peng Li (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Synergistic optimization of power matching and layout for fracturing–drilling equipment in extremely limited spaces via a hybrid GA–SA algorithm - Lei Zhang; Guangyu Yang; Bo Pan; Hua Liu; Yichao Li; Fulong Sun; Yunxiang Wang; Yue Sun; Huale Geng; Dongsheng Jiang (Computational Geosciences, 2026)
Fracturing operations for thick-roof control in underground coal mines—especially at the Hetaoyu Coal Mine in the Ordos Basin—are frequently restricted to extremely constrained workspaces (approximately 5,460 m $$^2$$ 2 ). Under such conditions, conventional experience-based planning often fails to simultaneously satisfy safety clearances, power-demand matching, and workflow efficiency. This paper proposes a synergistic power–layout optimization framework for fracturing–drilling equipment in minimal-area sites. First, a power–area coupling model is established to map functional power requirements to explicit spatial–geometric constraints. Second, a multi-objective optimization model is formulated to maximize site utilization while minimizing logistics costs and the center-of-mass (CoM) offset to enhance foundation stability. Third, a hybrid Genetic Algorithm–Simulated Annealing (GA–SA) algorithm is developed to solve the resulting nonlinear and highly constrained layout problem. Results show that the proposed GA–SA approach converges 31.7% faster than a standard GA. The optimized layout achieves 85.3% site utilization, limits the CoM offset to 1.23 m, and incorporates a dedicated fracturing operation lane to support high-pressure pumping operations. The proposed framework provides a quantitative and practical basis for safe, efficient drilling–fracturing integration in geotechnically sensitive sites with severely limited available area.

Co-direct reduction and electric smelting of preoxidized low-grade nickel laterite ore pellets for ferronickel production - Yunqing Liu; Xun Wang; Bo Li; Yonggang Wei; Hua Wang (Minerals Engineering, 2026)

Highly efficient recovery of gold by selective sulfide reduction from chlorine leachate - Qingfeng Ling; Shiwei Zhou; Bo Li; Yonggang Wei; Hua Wang (Journal of Cleaner Production, 2026)

Effect of chemical oxidants on the Pb-Cd-As co-contaminated soil solidified by waste-derived geopolymer: performance, mechanisms and environmental benefits - Zehai Li; Jun Yao; Shaoguang Hua; Shuqin Li; Kexin Li; Bo Ma (Environmental Research, 2026)

Machine learning-driven lipase engineering for highly enantioselective synthesis of chiral florfenicol intermediate via enzymatic resolution-chemical racemization coupling system - Jing-Peng Li; Hui-Hang Zhang; Zeng-Hua He; Jun-Bo Tian; Ren-Chao Zheng; Xiao-Ling Tang; Yu-Guo Zheng (Chemical Engineering Journal, 2026)

Physicochemical profiles and antioxidant capacities of lingzhi ( Ganoderma lingzhi ) polysaccharides under different extraction regimes - Huadan Liu; Jinhua Hua; Jinlong Xie; Bo Zhang; Shuang Hua; Xiao Li; Xiulian Duan (Natural Product Research, 2026)

Three phloridzin derivatives capable of anti-oxidant from Malus toringoides (Rehd) Hughes - Li Liu; Wei-wei Tian; Ying-chao Wang; Can Ren; Dong-mei Yu; Jian-bo Wang; Jun-ning Zhao; Hua Hua (Natural Product Research, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Atomic manufacturing enables order modulation in nanostructured alloys for ultrahigh strength–ductility synergy - Hang Zhao; Jing Zhou; Baoshuang Shang; Yuqiang Yan; Xing Tong; Xinxin Li; Haijie Xian; Yong Ding; Bo Zhang; Haibo Ke; Wei-Hua Wang (Science Bulletin, 2026)

Sonoporation-mediated bioremediation of DNAPLs: A synergistic approach integrating phase redistribution and genetic augmentation - Xiaoyang Wang; Wenjing Zhang; Juanfen Chai; Zhechao Hua; Hongyu Zhao; Shuxin Li; Bo Wan (Environmental Research, 2026)

Sensitization and gas-sensing mechanisms of recycled S-SnO2 from tin sludge for room-temperature SO2 detection - Tiangui Gao; Haoyuan Xu; Bo Li; Zepeng Li; Yonggang Wei; Hua Wang (Chemical Engineering Journal, 2026)

DrPISA: Deep eutectic solvent-assisted reverse proteome-integrated solubility alteration for high-sensitivity drug target identification - Liu Yang; Tian-Bo Ma; Chen-Wan Guo; Run-Bo Yu; Ping Li; Hua Yang; Wen Gao (Analytica Chimica Acta, 2026)

The climate threshold for locally absent rings in Siberian larch exhibits significant variation with altitude - Xiao-xia Gou; Tong-wen Zhang; Hua-ming Shang; Shu-long Yu; Dong Guo; Rui-bo Zhang; Li Qin; Sheng-xia Jiang; Yu-ting Fan; Ke-xiang Liu; He-li Zhang; Kai-long Guo; et al. (Agricultural and Forest Meteorology, 2026)

Y/Ho ratios in marine sediments unveil Neoproterozoic ocean acidification - Yong-Sheng Liu; Wen-Shuai Li; Jun-Bo Zhang; Jie Lin; Ao Yang; Lian Zhou; Dai-Du Fan; Xi Zhu; Ying-Hua Zhang (Science Bulletin, 2026)

Machine learning combined with the PMF model reveals the sources and driving factors of PAHs and Cl-PAHs in urban runoff - Li Li; Hai Huang; Pei Hua; Tao Chen; Jin Zhang; Peng Deng; Zongxi Zhao; Bo Yan (Journal of Environmental Sciences, 2026)

Molecular insight into the structure and formation mechanism of fluid phase in the classical coking theory - Bo Gong; Jie-Ping Wang; Hao-Dong Liu; Rui Guo; Jin-Xiao Dou; Guang-Yue Li; Ying-Hua Liang (Fuel, 2026)

YIP: optimized YOLOv11-seg for accurate intramuscular fat percentage prediction in pigs using non-invasive ultrasound imaging - Junhao Zhang; Hang Jiao; Genyuan Li; Hanhan Li; Chenglin Li; Pengsheng Dong; Yan Liu; Bo Jiang; Peng Shang; Feng Yang; Chunli Li; Xinjian Li; et al. (Science China Life Sciences, 2026)

Enhancing oil-water separation via droplet coalescence regulated by particle self-rotation in swirling fields - Wei Zhao; Ao-song Wei; Shu Zhu; Tong Zhang; Peng-bo Fu; Jian-ping Li; Xue-jing Yang; Hua-lin Wang (Water Research, 2026)

Generation, transformation and inhibition mechanism of hazardous waste flue coated materials during copper smelting process - Kai Fan; Haipei Zhang; Zhongming Jiang; Songhe Ye; Zhenqin Ge; Bo Li; Yonggang Wei; Shiwei Zhou; Hua Wang (Waste Management, 2026)

Single-Cell RNA Sequencing Reveals Impaired CHIP-Mediated Heat Stress Response in SCA3 Pathogenesis - Mi-bo Tang; Shi-feng Sheng; Zheng-wei Hu; Hai-yang Luo; Meng-jie Li; Shuo Zhang; Xiao-yan Hao; Cheng-yuan Mao; Shao-hua Li; Hui-fang Sun; Zhi-hua Yang; Yi Song; et al. (Molecular Neurobiology, 2026)

Screening and In Vivo Validation of Key Genes Involved in Myelin Damage in Alzheimer’s Disease - Hai-Tao Li; Ji-Wei Zhang; Bo-Wen Li; Hong-Yun Wu; Jin-Wen Ge; Da-Hua Wu; Quan-Lin Zhao; Ya-Han Wang (Molecular Neurobiology, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

Flow-Balanced Scheduled Routing and Robust Refueling for Inland LNG-Fuelled Liner Shipping - De-Chang Li; Kun Li; Yu-Hua Duan; Yong-Bo Ji; Zhou-Meng Ai; Fang-Fang Jiao; Hua-Long Yang (Journal of Marine Science and Engineering, 2025)
Inland LNG-fuelled liner shipping is emerging as a significant trend, yet limited refueling infrastructure presents operational challenges. The complexity of inland navigation requires frequent speed adjustments to meet scheduled arrivals, which directly affects fuel consumption and refueling strategies. Additionally, imbalances in domestic and foreign trade container flows further increase operating costs for liner shipping companies. Given estimated weekly demands, considering navigational restrictions such as water depth and bridge clearance, as well as streamflow velocity, port time windows, empty container repositioning, port selection, speed adjustment, and uncertain fuel consumption, two novel models based on empty container arc variables and node variables are formulated, aiming to maximize voyage profit. These models are extended from divisible demand to indivisible demand cases. The explicit expression for the maximum fuel consumption under the worst-case speed deviation is derived, and an external linear approximation algorithm is proposed to linearize the nonlinear models while controlling approximation errors. Furthermore, the NP-hardness of the problem, the strict equivalence of the two modeling approaches, and the solution properties are proved. A case study of LNG-fuelled liner shipping on the Yangtze River shows the following: (1) for divisible demand, both models achieve optimal solutions within seconds, while for indivisible demand, the node-variable model outperforms the arc-variable model; (2) tactical strategies should be flexibly adjusted based on seasonal water depth, fuel prices, carbon taxes, speed deviations, and expected lock passage times; and (3) increasing fuel prices and carbon taxes generally reduce port calls and sailing speeds, suggesting that stricter fuel price and carbon tax policies can support the transition to green shipping. This study provides both theoretical guidance and managerial insights, supporting shipping companies in optimizing operations and promoting the development of sustainable inland shipping.

Performance of heavy metals in the intertidal zone surface sediments of the Yellow River Estuary under water-sediment regulation scheme - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Ma; Feng Min Pan; Jian Wei Xing; Chen Long Feng; De Tong Tian; Zhi Bo Wang; Rui Wang (Marine Pollution Bulletin, 2025)

Machine learning-driven prediction and multi-objective optimization of pyrolysis behavior for waste printed circuit boards - Yunfeng Zhu; Bo Li; Yonggang Wei; Shiwei Zhou; Hua Wang (Sustainable Chemistry and Pharmacy, 2025)

One new rearranged pyranone derivative with antibacterial activity from Xylaria curta YSJ-5 - Shan-Shan Wei; Dao-Jun Rong; Jia-Ying Lai; Chen Chen; Si-Ran Li; Zhong-Hua Yu; Hai-Bo Tan (Phytochemistry Letters, 2025)

Metallothionein 2A alleviates ulcerative colitis by inhibiting ferroptosis in intestinal epithelial cells with Tfrc downregulation - Siqi Hua; Shuangshuang Song; Chunhao Yang; Jingwen Xu; Zhonghua Li; Bo Zhu; Zichun Hua (Journal of Trace Elements in Medicine and Biology, 2025)

A green and efficient process for extracting lithium from the clay-type lithium ore - Liyong Zhang; Shuang Shao; Bo Li; Hua Wang; Haipei Zhang; Yonggang Wei (Journal of Cleaner Production, 2025)

From sediment sinks to ice sinks: Differential phase partitioning of PAH derivatives in a cold-climate aquatic ecosystem - Bo Meng; Nan Jiang; Xin-Ming Guo; Jie Hu; Danilova Sakhayana Nikolaevna; Zakharov Moisei Ivanovich; Yi-Fan Li; Zi-Feng Zhang; Zhong-Hua Tang (Environmental Research, 2025)

Simultaneous recovery of valuable metals and detoxification of organics through co–smelting of waste printed circuit boards and copper slag - Yunfeng Zhu; Bo Li; Yonggang Wei; Shiwei Zhou; Hua Wang (Chemical Engineering Journal, 2025)

The connection between skeletal muscle and spinal canal membrane of Takifugu rubripes and its anatomical and physiological significance - Yang Song; Wen-Bin Jiang; Yu-Yu Xiong; Chun-Zhuo Shi; Hua-Xun Lai; Jing-Xian Sun; Lin-Lin Chen; Bo Liu; Yan-Yan Chi; Ji-Hang Li; Yi-Tong Sun; Xu-Hui Zhang; et al. (Frontiers in Marine Science, 2025)
Introduction The myodural bridge (MDB) is considered one of the circulatory dynamics of cerebrospinal fluid (CSF). Initially identified in the human neck, it has since been documented across diverse vertebrates, including fish with analogous “MDB-like” structures. The teleost Takifugu rubripes , which exhibits a high degree of genetic homology with humans, serves as an excellent model for such comparative studies. Investigating its MDB-like structure can therefore provide a morphological basis for elucidating the mechanism of CSF circulation and its evolution during the vertebrate land–water transition. Methods In this study, the morphology, development, and ultrastructure of MDB-like structure of Takifugu rubripes were explored. Three fresh adult T. rubripes were selected for gross anatomy. After incubation, 33 T. rubripes aged 13–120 days after hatching (dah) were fixed in 10% formalin solution. The samples aged 50–120 dah were further decalcified with EDTA for histological paraffin sectioning and Masson staining. Four cases aged 106 dah were fixed with 2.5% glutaraldehyde, two of which were observed by scanning electron microscopy, and two cases were observed by transmission electron microscopy. Results Through light microscopy and electron microscopy, the results of the current study is that there are three types of fiber connections (MDB-like) between skeletal muscle and the spinal canal membrane in T. rubripes : (1) The fibers from the myocomma attach to the spinal canal membrane; (2) The epimysium connects to the spinal canal membrane directly or connects to the spinal canal membrane through reticular, filamentous fibers, or fibers emitting from the perimysium; and (3) The fibers from the end of the muscle bundle stop at the spinal canal membrane. These connections mainly exist on the sides of each vertebral interspace and may function similarly to the MDB. Discussion Developmentally, “MDB-like” structures appeared in T. rubripes hatched at 18 dah, began to transmit force at 21 dah, and may have a positive correlation in development with the muscle and spinal canal membrane. This experiment provides developmental morphological information for comparative studies on the conservation and interspecies differences of MDB in evolution and provides informational support to explore the physiological function of MDB in humans.

Hypoglycemic cucurbitane-type triterpenoids from fruits of Citrullus colocynthis - Hua-Wei Lv; Yu Wan; Wen-Lin Fan; Meng-Di Zhu; Qiao-Liang Wang; Zhong-Bo Zhou; Chang-Chun Chen; Hong Wang; Xing-Nuo Li (Phytochemistry, 2025)

Advanced approach to sustainable recovery of valuable metals via co–smelting of waste printed circuit boards with copper smelting slag - Yunfeng Zhu; Bo Li; Yonggang Wei; Shiwei Zhou; Hua Wang (Chemical Engineering Journal, 2025)

Machine Learning-Based Classification of White Matter Functional Changes in Stroke Patients Using Resting-State fMRI - Li-Hua Liu; Chao-Xiong Wang; Xin Huang; Ri-Bo Chen (Brain Topography, 2025)

Rapid and highly sensitive mass spectrometric detection of n-alkanes via a novel photoionization-induced nitrogen dioxide cation chemical ionization source - Baimao Zhang; Bo Li; Lei Hua; Zhigang Fan; Guolong Wang; Hang Li; Heng Wang; Xiaopeng Li; Jichun Jiang; Haiyang Li (Analytica Chimica Acta, 2025)

Preparation of sponge indium by efficient cementation of indium tin oxide (ITO) waste target leachate - Yuyao Li; Xun Wang; Yonggang Wei; Bo Li; Hua Wang (Journal of Environmental Chemical Engineering, 2025)

Nano architectonics via in situ growth of MIL-101(Fe) on modified sugarcane bagasse for selective capture of glyphosate from aqueous solution - Ru-yi Zhou; Ming-hua Liu; Yun Xiao; Yu Qin; Bo Zuo; Muhammad Akhtar Abbas; Jun-xia Yu; Xiao-di Li; Yue-fei Zhang; Ru-an Chi (Journal of Environmental Chemical Engineering, 2025)

Proteome Profiling of Serum Reveals Pathological Mechanisms and Biomarker Candidates for Cerebral Small Vessel Disease - Yun-chao Wang; Hang-hang Zhu; Liu-Chang He; Ya-ting Yao; Lei Zhang; Xin-li Xue; Jing-yi Li; Li Zhang; Bo Song; Chang-he Shi; Yu-sheng Li; Yuan Gao; et al. (Translational Stroke Research, 2025)

Integrin CD11b Alleviates Cerebral Ischemia/Reperfusion Injury via a Mechanism Involving Microglia/Macrophage Polarization - Gui-Nan Jiang; Qiu-Yue Lin; Xiang-Bo An; Wei-Jia Yu; Jie Bai; Xin Yu; Feng Wang; Hui-Hua Li (Journal of Molecular Neuroscience, 2025)

Size-dependent diversity and accumulation of isoquinoline alkaloids in Corydalis yanhusuo tubers - Feng Jin; Honghong Jiao; Zhongxin Song; Mengyuan Zhang; Bo Li; Zhongyi Hua; Tianrui Liu; Pengjie Han; Zhishu Tang (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Rosmarinic acid in Perilla frutescens L. as a potential adenosine deaminase inhibitor: Preparation, machine learning validation and binding mechanism study - Bo-hao Liu; Zhong-Han Li; Bao-rong Wang; Jie Zhou; Bing Zhang; Kun-Long Wang; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

ERK-dependent and immunomodulatory in-situ injectable polyamino acid nanocomposite hydrogel reconstructs diabetic wound microenvironment for scarless wound healing - Penghui Wang; Yingying Yang; Wengjie Zhang; Jialing Li; Haifeng Shen; Jianqiang Wang; Hua Zhong; Shuang Li; Bo Chi (Chemical Engineering Journal, 2025)

Bioinspired neural network-enabled metre-scale attached ultraductile cementitious nanosensors with temperature-immune - Hua Fu; Penggang Wang; Heping Zheng; Bo Pang; Zuquan Jin; Xiaoyun Song; Li Tian; Zhenxing Du; Bukhari Mohd Nadeem; Peng Zhang; Zhengkai Hu (Chemical Engineering Journal, 2025)

Analysis on Inner Flow Field and Hydrodynamic Force on Flexible Mining Pipeline Under Bending States - Wen-Hua Wang; Lei Wang; Chuang Liu; Li-Jian Wang; Zi-Han Zhao; Lei-Lei Dong; Gang Liu; Ying-Ying Wang; Hai-Bo Sun; Kun Li (Journal of Marine Science and Engineering, 2025)
To investigate the internal flow characteristics of particles during hydraulic lifting in deep-sea mining risers, this study developed a three-dimensional curved riser multiphase flow model based on the Eulerian–Eulerian framework and the RNG k-ε turbulence model. The effects of particle distribution and pressure loss in the curved section, as well as the influence of curvature radius, were analyzed. Results indicate that particle distributions take concave circular or crescent-shaped patterns, becoming more uniform with larger curvature radii. Pressure on the extrados is consistently greater than on the intrados, with pressure loss increasing in the bend and peaking at the midpoint. A larger curvature radius leads to greater total pressure loss but lower frictional loss. Additionally, the bend experiences a restoring force toward the vertical position, which increases as the curvature radius decreases.

Architectural features and antioxidative biofunctionality of a novel pectin from Angelica keiskei Koidz - Si-Ru Chen; Yu-Ru Zhu; Li-Ting He; Hong-Liang Sun; Jing Huang; Yan-Zi Yang; Hua-Jun Zhao; Bo Yang; Meng-Xia Yan (Natural Product Research, 2025)

Corrigendum to “Fracture Characteristics of Granite Specimens after Heating-Cooling treatments: Insights from Experiments and GBM Simulations” [Comput. Geotech. 182 (2025) 107160] - Hao Yin; Yan-Hua Huang; Kun-Bo Zhang; Xue-Wei Liu; Jun Peng; Ming-Xu Li (Computers and Geotechnics, 2025)

Directed evolution of Escherichia coli Nissle 1917 functioning as a methylotrophic chassis - Li-Hua Liu; Zhiqian Zhang; Bo Xu; Gangzhu Yang; Hua Cui; Lijun Su; Yu Zhang; Baoqing Sun; Yi-Rui Wu; Ao Jiang (Chemical Engineering Journal, 2025)

Model test on dynamic response of coral sand in island dredging airport under wave, tidal and aircraft landing load - Jianxiu Wang; Ansheng Cao; Dongsheng Song; Bo Feng; Hua Zhang; Huboqiang Li; Yanxia Long; Zhenhua Ye (Marine Georesources & Geotechnology, 2025)

A hollow fiber supported ionic liquid membrane contactor for continuous extraction of lithium from high magnesium/lithium ratio brine - Bo Dong; Junyuan Hua; Jintao He; Jiahui Du; Jian Xiao; Jianxin Li (Water Research, 2025)

Ferroptosis is involved in the benzene-induced hematotoxicity via mitochondrial ROS-ferritinophagy pathway - Xiaohan Yang; Shuangyan Dong; Caihong Xing; Chao Li; Cunxiang Bo; Xiangjing Meng; Zhidan Liu; Hua Shao; Ming Li; Qiang Jia (Environmental Pollution, 2025)

The crucial role of vegetation cover in shaping the dipole pattern of East Asian summer monsoon changes during the late Pliocene warm period - Ruoxiao Gu; Xiangyu Li; Bo Liu; Hua Li; Zhongshi Zhang; Yong Liu (Quaternary Science Reviews, 2025)

Novel mechanisms for selenite biotransformation and selenium nanoparticles biogenesis in Acinetobacter sp. SX5 isolated from seleniferous soil - Sheng-Wei Huang; Yuan-yuan Yao; Hua-xu Zhang; Wan-ying Guo; Ming-hui Fang; Hai-bo Wang; Yu-jun Sun; Ming-hao Li (Journal of Hazardous Materials, 2025)

Fracture Characteristics of Granite Specimens after Heating-Cooling treatments: Insights from Experiments and GBM Simulations - Hao Yin; Yan-Hua Huang; Kun-Bo Zhang; Xue-Wei Liu; Jun Peng; Ming-Xu Li (Computers and Geotechnics, 2025)

Deep eutectic solvents for ginsenoside extraction and inhibition of ginsenoside hydrolysis in Panax notoginseng leaves: methodology and mechanistic insights - Jia-Yue Liu; Shi-Yao Hua; Li-Juan Ma; Xin Tao; Wen-Yu Fu; Jian-Bo Wan (Chemical Engineering Journal, 2025)

White matter microstructural and cognitive function changes in bipolar depression patients with suicidal ideation - Junfan Liang; Rui Fan; Xinyin Guo; Hua Liu; Xuehua Li; Jixiang Yuan; Kezhi Liu; Xuemei Liang; Bo Xiang (Brain Imaging and Behavior, 2025)

Cytotoxic metabolites from the mangrove endophytic fungus Aspergillus sp. GXNU QG1a - Xianglong Bo; Yufei Zhao; Feng Qin; Furong Wu; Meijing Tan; Shichao Ju; Zishuo Song; Wenjun Li; Fan He; Youquan Wei; Hua Xu; Xishan Huang (Natural Product Research, 2025)

Variation in climate and hydrological conditions in Southwest China during the mid-to-late Holocene, inferred from stalagmite multiple proxies - Hua-Yan Li; Yao Wu; Ting-Yong Li; Rong Duan; Hai-Bo Wang; Jia-Hui Cui; Chao-Jun Chen; Yue Jin; Yue-Hua Xiang; Zi-Qi Liu; Jun-Yun Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Synergistic effects of matrix metalloproteinases on the degradation of collagen in abalone (Haliotis discus hannai) - Yu-Lei Chen; Le-Le Su; Hua Liu; Tian-Bo Zhang; Guiling Li; Le-Chang Sun; Duanquan Lin; Tengchuan Jin; Ling-Jing Zhang; Min-Jie Cao (Food Chemistry, 2025)

Prospecting artificial microbial consortia toward lignin valorization - Jian-Ning Hu; Bo-Chao Gao; Zhi-Hua Liu; Xia Li; Ying-Jin Yuan; Bing-Zhi Li (Chemical Engineering Journal, 2025)

Sand Production and Critical Rate in Stress-Sensitive Unconsolidated Sandstone: An Experimental Study - Xiao-Hua Tan; Rui Wang; Xiao-Jun Zhou; Yao Zhu; Cai-Shen Li; Bo Cao; Zhi Yang; Hao Chen; Bao-Quan Wen; Liu Tang; Huan-Yu Ran (Geotechnical and Geological Engineering, 2025)

A promising approach for efficient and selective extraction of lithium from clay-type lithium resource: Process optimization and reaction mechanism - Huan Qiu; Shuang Shao; Ba Zhang; Bo Li; Hua Wang; Yonggang Wei (Process Safety and Environmental Protection, 2025)

A Gln alteration influences leaf morphogenesis by mediating gibberellin levels in tobacco - Qi-Li Mi; Hong-Tao Lv; Fei-Fei Huang; Li Xu; Zi-Ying Huang; Wen-Wu Yang; Mei-Yun Zou; Hai-Tao Huang; Wan-Li Zeng; Jia-Yin Zhao; Qing-Xian Chen; Yong-En Si-Tu; et al. (Journal of Plant Physiology, 2025)

Experimental behaviour of concrete-filled double-skin corrugated steel tubes under combined compression and cyclic lateral loads - Bo Lu; Yong Fang; Yuyin Wang; Hua Yang; Hao Li (Engineering Structures, 2025)

A New Pattern of Species Diversification Revealed by Populus on the Qinghai-Tibet Plateau - Jia-Xuan Mi; Fei-Fei Tian; Jin-Liang Huang; Yu-Jie Shi; Jing Li; Fan-Yu Meng; Fang He; Yu Zhong; Han-Bo Yang; Fan Zhang; Liang-Hua Chen; Xue-Qin Wan (Evolutionary Biology, 2025)

Geochemical characteristics and environmental implications of heavy metals and fluoride of the hot spring waters in China’s Tengchong Geothermal Field - Bo Xia; Lan Jiang; Yufei Yuan; Hua Tang; Xiaocheng Zhou; Jiao Tian; Miao He; Yongxian Zhang; Xiaoyi Zhu; Jiang Li; Dan Zhou; Yi Huang (Environmental Science and Pollution Research, 2025)

Research on high-temperature fast pyrolysis of waste printed circuit boards for gas release and carbon structure evolution - Yunfeng Zhu; Bo Li; Yonggang Wei; Shiwei Zhou; Hua Wang (Waste Management, 2025)

2.08 Ga andesitic gneisses in the southwestern Yangtze Block: Unveiling new insights into its geological evolution - Jun-Ping Liu; Zai-Bo Sun; Wei-Ke Li; Hua-Li Luo; Shi-Jun He; Shao-Bin Hu; Jiang-Tai Zhao; Hai-bao Yan; Ming-Guo Zhai; Hai-Long He (Precambrian Research, 2025)

Electrospun dibenzo-18-crown-6 polyimide dendritic nanofiber membranes for efficient adsorption separation of cesium - Jian Xiao; Feidong Yang; Jintao He; Junyuan Hua; Bo Dong; Xiaohua Ma; Zhenyu Cui; Jianxin Li (Journal of Environmental Chemical Engineering, 2025)

Microplastics release from infant feeding bottles and milk storage bags - Long Zhao; Yiying Gu; Hua Cai; Xin Xu; Jianguo Yu; Jing Li; Ying Shen; Leiyan Zhu; Yan Jin; Mei Zhang; Ruihua Dong; Bo Chen (Food Control, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Application of 18β-glycyrrhetinic acid in the structural modification of natural products: a review - Wan-Xin Li; Ye-Fang Lu; Fei Wang; Bing Ai; Sheng-Bo Jin; Siqi Li; Guang-Hua Xu; Cheng-Hua Jin (Molecular Diversity, 2025)

Sealing Integrity Evaluation and Optimization of Cement Sheath-Formation Interface under Different Formation Conditions during Fracturing - Donghua Su; Sheng Huang; Zaoyuan Li; Jin Li; Ziyu Wang; Shizhong Tang; Hua Wu; Bo Zhao (Journal of Earth Science, 2025)

Amine antioxidants in water, ice, sediment and soil from the Songhua Wetland, Northeast China: Occurrence and fate - Jie Hu; Tian-Wei Xu; Ye Zhang; Meng-Yuan Xiao; Bo Meng; Vasiliy Egorovich Kolodeznikov; Natalia Nikolaevna Petrova; Vasilii Vasilevich Mukhin; Zi-Feng Zhang; Zhong-Hua Tang; Yi-Fan Li (Science of The Total Environment, 2025)

Chaos enhanced leaching of indium from indium tin oxide (ITO) waste targets - Yuyao Li; Xun Wang; Yonggang Wei; Bo Li; Hua Wang (Journal of Cleaner Production, 2025)

Flexural performance and crack width prediction of steel-UHTCC composite bridge decks with wet joints - Jing-Zhong Tong; Yun-Long Chen; Qing-Hua Li; Jian-Bo Dai; Guo-Zhong Wang; Jia-Jia Shen; Wei Gao; Shi-Lang Xu (Engineering Structures, 2025)

Effects of imidacloprid on Orius similis: assessing growth, development, and reproduction through age-stage two-sex life table analysis under contact and stomach toxicity treatments - Bo Zhang; Yi-Ru Li; Jin-Long Zhang; Guo-Hua Chen; Nian Yang; Ji-Huan Liu; Guo-Ting Yuan; Xiao-Ming Zhang (Journal of Pest Science, 2025)

High-affinity potassium transporter TaHAK1 implicates in cesium tolerance and phytoremediation - Jin Liu; Shuai-Bo Chen; Ze-Hua Fan; Haitao Liu; Yinglong Chen; Chandra Shekhar Seth; Evgenios Agathokleous; Tian-Cai Guo; Guo-Zhang Kang; Ge-Zi Li (Journal of Hazardous Materials, 2024)

Preparation of umami peptides from chicken breast by ultrasound-assisted gradient dilution feeding substrate and study of their formation mechanism - Jing Guo; Xiaojie Yu; Cunshan Zhou; Bo Wang; Lei Zhang; Phyllis Otu; Li Chen; Yunwei Niu; Deyang Yao; Chenhui Hua; Haile Ma (Food Bioscience, 2024)

Hepcidin defense patterns in intestine of mandarin fish (Siniperca chuatsi) against Aeromonas hydrophila infection - Jin-hua Gao; Jin-liang Zhao; Ning-xin Guo; Temesgen Tola; Wen-bo Xue; Kang-ning Cai; Xiao-li Yao; Miao Hu (Fish & Shellfish Immunology, 2024)

Comparative Analysis of Seven Endogenous Hormones in a Novel Dual-axillary Bud Mutant Genotype of Sugarcane - Kamal Priyananda Wickramasinghe; Jun Mao; Chao-hua Xu; Xiu-qin Lin; Xu-juan Li; Wei Qin; Hong-bo Liu; Xin-long Liu; Faisal Mehdi; Pei-fang Zhao; Xin Lu (Sugar Tech, 2024)
The sugarcane genotype YZ 07-86 is a distinct natural mutant with dual-axillary buds. Exploitation of this valuable trait in sugarcane breeding requires an understanding of the physiological mechanism of dual-axillary bud formation. This experiment determined the contents of indole-3-acetic acid (IAA), abscisic acid (ABA), gibberellins (GA 3 and GA 4 ), and three cytokinins (CKs), namely isopentenyl adenosine (iPA), zeatin riboside (ZR), and dihydrozeatin riboside (DHZR), in the shoot apical meristem tissues of YZ 07-86 and its sister line YZ 07-87, which served as the control genotype. The field experiment followed a completely randomized design with three replications for each genotype. Sampling was done at 5-day intervals, starting 106 days after planting. The ELISA technique was used to measure the contents of endogenous hormones. The study revealed that the mean contents of IAA, GA 3 , GA 4 , DHZR, and iPA were not significantly different ( P > 0.05) among the genotypes. Conversely, in YZ 07-86, the mean ZR content was significantly higher ( P < 0.05), and the mean ABA content was significantly lower than in the control genotype. Moreover, the mean content ratios of ZR/IAA, ZR/ABA, ZR/GA 3 , and ZR/GA 4 were also significantly higher in YZ 07-86. The study concludes that elevated ZR content and an increased ZR/ABA ratio directly contributes to dual-axillary bud formation in YZ 07-86, offering valuable insights for the advancement of sugarcane genotypes.

MEIKIN expression and its C-terminal phosphorylation by PLK1 is closely related the metaphase–anaphase transition by affecting cyclin B1 and Securin stabilization in meiotic oocyte - Li-Hua Fan; Shu-Tao Qi; Zhen-Bo Wang; Ying-Chun Ouyang; Wen-Long Lei; Yue Wang; Ang Li; Feng Wang; Jian Li; Li Li; Yuan-Yuan Li; Yi Hou; et al. (Histochemistry and Cell Biology, 2024)

Suppression of seismic random noise by deep learning combined with stationary wavelet packet transform - Hua Fan; Dong-Bo Wang; Yang Zhang; Wen-Xu Wang; Tao Li (Applied Geophysics, 2024)

Noradrenergic Projections from the Locus Coeruleus to the Medial Prefrontal Cortex Enhances Stress Coping Behavior in Mice Following Long-Term Intermittent Fasting - Zheng Zhao; Jun-Liang Chen; Han Zhan; Chang-Rong Fang; Li-Bo Hua; Hao-Yuan Deng; Zongqin Xiang; Ying Yang; Lang Huang; Yong U. Liu (NeuroMolecular Medicine, 2024)

CBR-470-1 protects against cardiomyocyte death in ischaemia/reperfusion injury by activating the Nrf2–GPX4 cascade - Ze-Yang Qiu; Kai-Na Shi; Hui-Hua Li; Bo Zhang (Toxicology and Applied Pharmacology, 2024)

Mechanism of discoloration of Antarctic krill oil upon storage: A study based on model systems - Xiang-Bo Zeng; Xue-Chen Pei; De-Yang Li; Fa-Wen Yin; Hui-Lin Liu; Meng-Ling Jin; Jiang-Hua Zhang; Da-Yong Zhou (Food Chemistry, 2024)

Tuning anchoring groups of “Y-Type” self-assembled hole transport materials for interface passivation in inverted perovskite solar cells - Yimeng Li; Xin Luo; Yuqi Yan; Xiangbin Tian; Haitao Zhou; Zhenyuan Xia; Kunpeng Guo; Jinhai Huang; Bo Xu; Hua Wang (Chemical Engineering Journal, 2024)

Study on Preclinical Safety and Toxic Mechanism of Human Umbilical Cord Mesenchymal Stem Cells in F344RG Rats - Xiaofang Hao; Hao Zhu; Chao Qin; Lulu Li; Zhi Lin; Hua Jiang; Qianqian Li; Yan Huo; Hezhan Zhang; Xingchao Geng; Ying Huang; Bo Li (Stem Cell Reviews and Reports, 2024)

Zika virus infection induces glycometabolic disorder in northern pig-tailed macaques - Qing Li; Ren-Hua Yang; Yan Hu; Bei-Bei Tang; Ying-Jie Jiang; Chang-Bo Zheng; Tian-Zhang Song (Science China Life Sciences, 2024)

Response Mechanism of Dynamic Tensile Mechanics in Granite Under Microwave Irradiation: Insights from Experiments and Simulations - Bo-Wen Sun; Sheng-Qi Yang; Man Huang; Heng Li; Wen-Ling Tian; Yan-Hua Huang (Rock Mechanics and Rock Engineering, 2024)

Treatment of swine manure by hydrothermal carbonization: The influential effect and preliminary mechanism of surfactants - Zhen-tian Feng; Jiang-bo Xiong; Guo-feng Wang; Lin Li; Chun-fei Zhou; Chun-huo Zhou; Hua-jun Huang (Science of The Total Environment, 2024)

Lappanolides A−N, fourteen undescribed sesquiterpenoids from Saussurea costus (Syn. Saussurea lappa) and their anti HBV activity - Hong-Bo Li; Shi-Qun Bai; Teng-Yun Shu; Qiong Wang; Hao Chen; Li-Hua Su; Min Xu (Phytochemistry, 2024)

Disinfection of bacteria and viruses under near infrared light by tunable self-assembled nanomaterial NH2-MIL-101-xAu based on photothermal and photodynamic mechanisms - Nian Li; Zi-jian He; Jia-min Gan; Xing-rui Qi; Shu-nuo Bian; Yu-fang Chen; Bo Liu; Hua-jie Lai; Tao Jin (Journal of Environmental Chemical Engineering, 2024)

Effects of Se-enriched yeast on the amelioration of atrazine-induced meat quality degradation - Cong Zhang; Yu Liu; Peilin Wang; Bo Wang; Shanshan Zhang; Zeao Hua; Yanan Li; Xuebing Wang; Xu Yang (Food Chemistry, 2024)

The LINGO-1-deficient neural stem cell-derived neural tissueoid showed enhanced retention and neuronal relay in the transected spinal cord - Ge Li; Li-Jun Huang; Bao Zhang; Shu Liu; Jing-Hua Liang; Ying Ding; Xiang Zeng; Bi-Qin Lai; Yuan-Huan Ma; Ya-Qiong Wang; Rui Wang; Hong-Bo Zhang; et al. (Chemical Engineering Journal, 2024)

Effects of Spraying Allantoin at Different Stages on Inorganic Nitrogen Assimilation, Endogenous Hormones, Yield, and Quality of Sugar Beet in Saline-Alkali Land - Xin-Rui Yu; Jia-Nan Zhao; Yan-Long Zhuang; Ling-Hua Zhao; Chao Wang; Xiao-Fei Yang; Yu-Bo Wang; Cai-Feng Li (Sugar Tech, 2024)

Enhancing CO2 storage and marine carbon sink based on seawater mineral carbonation - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Shuo Chen Li; Zhi Bo Wang; Jun Ma (Marine Pollution Bulletin, 2024)

The influence of chlorination additives on metal separation during the pyrometallurgical recovery of spent lithium-ion batteries - Guorui Qu; Yonggang Wei; Bo Li; Hua Wang (Waste Management, 2024)

Monoterpene-chalcone conjugates and diarylheptanoids isolated from the seeds of Alpinia katsumadai Hayata with cytotoxic activity - Hua-Lin You; Bo Zhou; Meng-Jia Guo; Xin-Man Zhao; Xiao-Long Li; Xiang-Chun Shen; Nen-Ling Zhang (Phytochemistry, 2024)

Simultaneous enhancement of ductility and sustainability of high-strength Strain-Hardening Cementitious Composites (SHCC) using recycled fine aggregates - Qing-Hua Li; Shu-Yue Zhao; Bo-Tao Huang; Ling-Yu Xu; Shi-Lang Xu (Journal of Cleaner Production, 2024)

Bond behavior between steel bar and strain-hardening fiber-reinforced cementitious composites under fatigue loading - Qing-Hua Li; Ai-Min Luo; Bo-Tao Huang; Guo-Zhong Wang; Shi-Lang Xu (Engineering Structures, 2024)

Development and efficacy evaluation of nanoliposomes targeting CAFs-LCSCs communication for hepatocellular carcinoma treatment - Liang Kong; Yang Yu; Ru Yang; Rui-bo Guo; Lu Zhang; Jia-hua Wang; Yang Liu; Juan Zang; Chen Yang; Hui-yue Yang; Rui-jun Ju; Xue-tao Li (Chemical Engineering Journal, 2024)

Permeability Estimation of Shale Oil Reservoir with Laboratory-derived Data: A Case Study of the Chang 7 Member in Ordos Basin - Lin Zhang; Li Gao; Jing Ba; Meng-Bo Zhang; José M. Carcione; Wei-Hua Liu (Applied Geophysics, 2024)

Economic life evaluation of reservoir dams based on comprehensive costs and benefits analysis considering potential dam breach: A case study of the Luhun reservoir in China - Wei Ge; Heqiang Sun; Laihong Jing; Zongkun Li; Yongchuang Li; Bo Cao; Te Wang; Yutie Jiao; Hua Zhang; Jianyou Wang; Pieter van Gelder (Journal of Hydrology, 2024)

Exposure to 1-nitropyrene after weaning induces anxiety-like behavior partially by inhibiting steroid hormone synthesis in prefrontal cortex - Xiao-Xi Chen; Bo Wang; Wei Cai; Yi-Hao Zhang; Li Shen; Yan-Yan Zhu; Tao Wang; Xiu-Hong Meng; Hua Wang; De-Xiang Xu (Journal of Hazardous Materials, 2024)

An empirical model for prediction of centimeter wave attenuation during haze event considering particle humidity and charge - Tian-Li Bo; Xiao-Hua Yang; Zhi-Mei Huang (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Development of an ELISA method to determine adulterated cow milk in camel milk - Shi-Xin Chi; Bo-Hao Liu; Bing Zhang; Bao-Rong Wang; Jie Zhou; Ling Li; Ying-Hua Zhang; Zhi-shen Mu (International Dairy Journal, 2024)

A highly efficient ternary extraction system with tributyl phosphate/crown ether/NaNTf2 for the recovery of Li+ from low-grade salt lakes - Junyuan Hua; Feidong Yang; Jintao He; Jiahui Du; Bo Dong; Xiaohua Ma; Jianxin Li (Desalination, 2024)

Soil improvement using biostimulated MICP: Mechanical and biochemical experiments, reactive transport modelling, and parametric analysis - Yi-jie Wang; Wen-bo Chen; Peng-lin Li; Zhen-yu Yin; Jian-hua Yin; Ning-jun Jiang (Computers and Geotechnics, 2024)

Recycled lower oceanic crust signal in early Jurassic A1-type granites, South China: Implications for flat-slab subduction and mantle heterogeneity in the continental back-arc region - Bo Yan; Wu-Xian Li; Xiao-Long Huang; Ji-Hua Tao (Chemical Geology, 2024)

Joint influence of the North Atlantic sea surface temperature and the Barents sea-ice concentration on the dipole pattern of Eurasian surface air temperature in March - Yuan Yuan; Huixin Li; Bo Sun; Shengping He; Fei Li; Hua Li (Atmospheric Research, 2024)

Identification of the Galactinol Synthase (GolS) Family in Medicago truncatula and Expression Analysis Under Abiotic Stress and Phytohormone Treatment - Hua Li; Ying Di Gao; Li Qing Kang; Hong Yang Yu; Li Ming Zeng; Yi Hua Wang; Rong Rong Chen; Jian Bo Song (Journal of Plant Growth Regulation, 2024)

Multiple Matching Attenuation Based on Curvelet Domain Extended Filtering - Qingfeng Hua; Zhang Chen; Huili He; Jun Tan; Haifeng Chen; Guanbao Li; Peng Song; Bo Zhao; Xiuping Jiang (Journal of Ocean University of China, 2024)

Rapid, sensitive, and visual detection of pseudorabies virus with an RPA-CRISPR/EsCas13d-based dual-readout portable platform - Dong You; Tong Xu; Bing-Zhou Huang; Fang Wu; Li-Shuang Deng; Zhe-Yan Liu; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; Yuan-Cheng Zhou; Si-Yuan Lai; et al. (Analytica Chimica Acta, 2024)

Experimental evidence that nitrogen-fixing cyanobacterium Trichodesmium spp. supplies new nitrogen source to marine phytoplankton - Shuang-Qing Li; Yan Xiao; Hai-Long Huang; Zhen Luo; Tao-Ran Sun; Hua-Yang Gao; Xin-Wei Wang; Hai-Bo Jiang (Frontiers in Marine Science, 2024)
In oligotrophic oceans, primary productivity is widely limited by nitrogen bioavailability. The broadly distributed and abundant nitrogen-fixing cyanobacterium Trichodesmium plays an important role in the oceanic nitrogen and carbon cycles by providing a “new” source of nitrogen to many non-diazotrophic microbes, thereby driving new primary production in the ocean. However, the underlying process and mechanism of nitrogen supply from Trichodesmium to other phytoplankton remain unclear. Here, our results demonstrated that the fixed nitrogen released by Trichodesmium could sustain the growth of a non-nitrogen-fixing cyanobacterium Synechococcus sp. PCC 7002, including a mutant strain (Mut- ureA ) that cannot use urea. However, the growth rate of Mut- ureA was approximately 20% lower than that of the wild strain when Trichodesmium filtrate was used for nitrogen supply. This result was consistent with the composition of the Trichodesmium exudate, in which urea comprised more than 20% of the total fixed nitrogen that was released. It is evident from the experiments that a fraction of the Trichodesmium -derived nitrogen was not available to Mut- ureA . Our results suggested that Trichodesmium produces dissolved organic nitrogen, especially a certain amount of urea as a “new” nitrogen source, benefiting in particular populations of surrounding phytoplankton species.

Correction to: Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao‑Bo Li; Yan‑Xun Han; Zi‑Yue Fu; Yu‑Chen Zhang; Min Fan; Shu‑Jia Sang; Xi‑Xi Chen; Bing‑Yu Liang; Yu‑Chen Liu; Peng‑Cheng Lu; Hua‑Wei Li; Hai‑Feng Pan; et al. (Environmental Science and Pollution Research, 2024)

Prenatal exposure to fenvalerate causes depressive-like behavior in adulthood by inhibiting brain-derived 5-HT synthesis - Hui-Min Zhu; Bo Wang; Tao Wang; Jing Shao; Hui-Ru Chen; Chi Zhang; Li-Hua Xu; Jing-Jing Li; Min Wang; De-Xiang Xu; Xiu-Hong Meng (Environmental Pollution, 2024)

Human umbilical cord mesenchymal stem cells attenuate diabetic nephropathy through the IGF1R-CHK2-p53 signalling axis in male rats with type 2 diabetes mellitus - Hao Zhang; Xinshu Wang; Bo Hu; Peicheng Li; Yierfan Abuduaini; Hongmei Zhao; Ayinaer Jieensihan; Xishuang Chen; Shiyu Wang; Nuojin Guo; Jian Yuan; Yunhui Li; et al. (Journal of Zhejiang University-SCIENCE B, 2024)

Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao-Bo Li; Yan-Xun Han; Zi-Yue Fu; Yu-Chen Zhang; Min Fan; Shu-Jia Sang; Xi-Xi Chen; Bing-Yu Liang; Yu-Chen Liu; Peng-Cheng Lu; Hua-Wei Li; Hai-Feng Pan; et al. (Environmental Science and Pollution Research, 2024)
Air pollution can cause disease and has become a major global environmental problem. It is currently believed that air pollution may be related to the progression of SSNHL. As a rapidly developing city in recent years, Hefei has serious air pollution. In order to explore the correlation between meteorological variables and SSNHL admissions, we conducted this study. This study investigated the short-term associations between SSNHL patients admitted to the hospital and Hefei climatic variables. The daily data on SSNHL-related hospital admissions and meteorological variables containing mean temperature (T-mean; °C), diurnal temperature range (DTR; °C), atmospheric pressure (AP; Hp), and relative humidity (RH; %), from 2014 to 2021 (2558 days), were collected. A time-series analysis integrating distributed lag non-linear models and generalized linear models was used. PubMed, Embase, Cochrane Library, and Web of Science databases were searched. Literature published up to August 2023 was reviewed to explore the potential impact mechanisms of meteorological factors on SSNHL. The mechanisms were determined in detail, focusing on wind speed, air pressure, temperature, humidity, and air pollutants. Using a median of 50.00% as a baseline, the effect of exceedingly low T-mean in the single-day hysteresis effect model began at a lag of 8 days (RR = 1.032, 95% CI: 1.001 ~ 1.064). High DTR affected the admission rate for SSNHL on lag 0 day. The significance of the effect was the greatest on that day (RR = 1.054, 95% CI: 1.007 ~ 1.104) and then gradually decreased. High and exceedingly high RH affected the admission rate SSNHL on lag 0 day, and these effects lasted for 8 and 7 days, respectively. There were significant associations between all grades of AP and SSNHL. This is the first study to assess the effect of meteorological variables on SSNHL-related admissions in China using a time-series approach. Long-term exposures to high DTR, RH values, low T-mean values, and all AP grades enhance the incidence of SSNHL in residents. Limiting exposure to extremes of ambient temperature and humidity may reduce the number of SSNHL-related hospital visits in the region. It is advisable to maintain a suitable living environment temperature and avoid extreme temperature fluctuations and high humidity. During periods of high air pollution, it is recommended to stay indoors and refrain from outdoor exercise.

Overlooked in-situ sulfur disproportionation fuels dissimilatory nitrate reduction to ammonium in sulfur-based system: Novel insight of nitrogen recovery - Bo Shao; Li Niu; Yuan-Guo Xie; Ruochen Zhang; Wei Wang; Xijun Xu; Jianxing Sun; Defeng Xing; Duu-Jong Lee; Nanqi Ren; Zheng-Shuang Hua; Chuan Chen (Water Research, 2024)

Turbulent transports in the flow around a rectangular cylinder with different aspect ratios - Jiang-hua Li; Bo-fu Wang; Xiang Qiu; Quan Zhou; Shi-xiao Fu; Yu-lu Liu (Ocean Engineering, 2024)

Mechanism of color change in Antarctic krill oil during storage - Xiang-Bo Zeng; Fa-Wen Yin; Guan-Hua Zhao; Chao Guo; De-Yang Li; Hui-Lin Liu; Lei Qin; Fereidoon Shahidi; Da-Yong Zhou (Food Chemistry, 2024)

Amanitin-induced variable cytotoxicity in various cell lines is mediated by the different expression levels of OATP1B3 - Mengqiang Gong; Zhi Li; Hua Xu; Bo Ma; Pengxia Gao; Lili Wang; Junkai Li; Qinglai Wu; Jianfeng Wu; Jianwei Xie (Food and Chemical Toxicology, 2024)

Zinc as a potential regulator of the BCR-ABL oncogene in chronic myelocytic leukemia cells - Bo Zhu; Longshuo Sun; Zhonghua Li; Pengyou Shang; Chunhao Yang; Kaiqiang Li; Jiahuang Li; Qi Zhi; Zichun Hua (Journal of Trace Elements in Medicine and Biology, 2024)

Green manure substitution for potassium fertilizer promotes agro-ecosystem multifunctionality via triggering interactions among soil, plant and rhizosphere microbiome - Qing Zeng; Mei Yin; Li-Bo Fu; Brajesh K. Singh; Si-Yi Liu; Hua Chen; An-Hui Ge; Li-Li Han; Li-Mei Zhang (Plant and Soil, 2024)

Pseudocercones A-C, three new polyketide derivatives from the endophytic fungus Pseudocercospora sp. TSS-1 - Wei-Wei Peng; Min Kuang; Yuan-Tao Huang; Mei-Fang Li; Yu-Ting Zheng; Li Xu; Jian-Bing Tan; Feng-Hua Kang; Hai-Bo Tan; Zhen-Xing Zou (Natural Product Research, 2024)

Crystal mush rejuvenation in the formation of Triassic dacites in Mengku, SE Tibetan Plateau - Feng Cong; Fu-Yuan Wu; Wen-Chang Li; Zai-Bo Sun; Xiao-Chi Liu; De-Feng He; Wei-Qiang Ji; Fang-Yang Hu; Shao-Hua Zhang; Xiao-Ming Huang (Journal of Asian Earth Sciences, 2024)

All-fluorescent white organic light-emitting diodes employing a deep-blue HLCT material simultaneously as emitter and host achieving excellent electroluminescence performance with efficiency roll-off <1 % at 1000 cd/m2 - Xiaoxia Li; Xiyu Wang; Huixia Xu; Bo Zhao; Yuanyuan Guo; Yanqin Miao; Baoyou Liu; Gang Yue; Hua Wang (Chemical Engineering Journal, 2024)

Dual fluorescence induced thermally activated delayed fluorescence materials based on 2,4-Diphenylthieno[3,2-d]pyrimidine with an efficient single-molecular white electroluminescence - Xiangbin Tian; Shu Xiao; Jing Sun; Jiakui Yan; Guozheng Li; Bo Zhao; Yanqin Miao; Long Wang; Hua Wang; Dongge Ma (Chemical Engineering Journal, 2024)

Effects of arcade design on wind and thermal environment inside an idealized 2D urban canyon with realistic solar heating - Jian Hang; Qingman Li; Yaxing Du; Jiaxi Feng; Jiajia Hua; Bo Zhao (Building and Environment, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

An anomalous rollback process of Mesozoic flat-slab subduction in South China - Bo Yan; Wu-Xian Li; Xiao-Long Huang; Yang Yu; Ji-Hua Tao (Tectonophysics, 2024)

Divinyl sulfone, an oxidative metabolite of sulfur mustard, induces caspase-independent pyroptosis in hepatocytes - Zhi Li; Bo Ma; Hua Xu; Mengqiang Gong; Pengxia Gao; Lili Wang; Jianwei Xie (Archives of Toxicology, 2024)

Exposure to ambient air pollution and chronic bronchitis: Findings from over 6.6 million adults in northwestern China - Weidong Ji; Yushan Wang; Xiao-Xuan Liu; Lin Li; Hua Yao; Yi Zhou; Bo-Yi Yang (Chemosphere, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Adsorption performance and mechanism of TiO2/PVDF-based lithium-ion imprinted membrane in leaching solution of spent lithium-ion batteries - Guorui Qu; Jiaqi Yang; Yuxuan Ran; Bo Li; Hua Wang; Yonggang Wei (Journal of Cleaner Production, 2024)

Catalytic pyrolysis of waste printed circuit board with copper slag for the production of H2-rich gas - Yunfeng Zhu; Bo Li; Yonggang Wei; Shiwei Zhou; Hua Wang (Fuel, 2024)

Biogas upgrading by biotrickling filter: Effects of temperature and packing materials - Jie-Hua Huang; Xiao-Lei Fan; Rui Li; Meng-Ting Sun; Hua Zou; Yi-Feng Zhang; Rong-Bo Guo; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Diagenetic effects on strontium isotopes in shallow-water carbonate sediments from Middle Miocene to Recent - Xinran Chen; Mengchun Cao; Thomas J. Algeo; Na Li; Guang-yi Wei; Yi-bo Lin; Hua Zhang; Lei Xiang; Youhua Zhu; Changgui Xu; Caiwei Fan; Shuzhong Shen; et al. (Chemical Geology, 2024)

Physicochemical properties of clayey deposits slurry treated by lime-activated ISSA and GGBS considering seawater salinity effect - Zhao Sun; Wen-Bo Chen; Run-Dong Zhao; Jiang-Shan Li; Zhen-Yu Yin; Jian-Hua Yin; Yong-Gui Chen (Applied Clay Science, 2024)

Epidermal growth factor: Expression in goat endometrial epithelia during early pregnancy and regulation by interferon tau and FOXO1 - Bo Wang; Meng-Die Li; Hai-Yue Xu; Xin-Cheng Zhang; Li-Ge Bu; Ting-Yue Li; Ya Sun; Hua Ni (Animal Reproduction Science, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

Efficient separation and extraction of lithium from low-grade claystone by chloride salt-enhanced roasting process - Yuxuan Ran; Guorui Qu; Jiaqi Yang; Shiwei Zhou; Bo Li; Hua Wang; Yonggang Wei (Journal of Cleaner Production, 2024)

Mechanism for metal loss in smelting of recycled spent lithium-ion batteries: The overlooked role of refractory materials - Guorui Qu; Jiaqi Yang; Yonggang Wei; Shiwei Zhou; Bo Li; Hua Wang (Journal of Environmental Management, 2024)

Identification of antimicrobial peptide genes from transcriptomes in Mandarin fish (Siniperca chuatsi) and their response to infection with Aeromonas hydrophila - Jin-hua Gao; Jin-liang Zhao; Xiao-li Yao; Temesgen Tola; Jia Zheng; Wen-bo Xue; Da-wei Wang; Ying Xing (Fish & Shellfish Immunology, 2024)

Agglomeration inhibition mechanism of SiO2 in the Ca(OH)2/CaO thermochemical heat storage process: A reactive molecular dynamics study - Kun Wang; Cheng-Ming Zhang; Bo-Chao Liu; Li Yang; Chun-Hua Min; Zhong-Hao Rao (Chemical Engineering Journal, 2024)

Human activity and climate change accelerate the extinction risk to non‐human primates in China - Wen‐Bo Li; Yang Teng; Ming‐Yi Zhang; Ying Shen; Jia‐Wen Liu; Ji‐Wei Qi; Xiao‐Chen Wang; Rui‐Feng Wu; Jin‐Hua Li; Paul A. Garber; Ming Li (Global Change Biology, 2024)
Human activity and climate change affect biodiversity and cause species range shifts, contractions, and expansions. Globally, human activities and climate change have emerged as persistent threats to biodiversity, leading to approximately 68% of the ~522 primate species being threatened with extinction. Here, we used habitat suitability models and integrated data on human population density, gross domestic product (GDP), road construction, the normalized difference vegetation index (NDVI), the location of protected areas (PAs), and climate change to predict potential changes in the distributional range and richness of 26 China's primate species. Our results indicate that both PAs and NDVI have a positive impact on primate distributions. With increasing anthropogenic pressure, species' ranges were restricted to areas of high vegetation cover and in PAs surrounded by buffer zones of 2.7–4.5 km and a core area of PAs at least 0.1–0.5 km from the closest edge of the PA. Areas with a GDP below the Chinese national average of 100,000 yuan were found to be ecologically vulnerable, and this had a negative impact on primate distributions. Changes in temperature and precipitation were also significant contributors to a reduction in the range of primate species. Under the expected influence of climate change over the next 30–50 years, we found that highly suitable habitat for primates will continue to decrease and species will be restricted to smaller and more peripheral parts of their current range. Areas of high primate diversity are expected to lose from 3 to 7 species. We recommend that immediate action be taken, including expanding China's National Park Program, the Ecological Conservation Redline Program, and the Natural Forest Protection Program, along with a stronger national policy promoting alternative/sustainable livelihoods for people in the local communities adjacent to primate ranges, to offset the detrimental effects of anthropogenic activities and climate change on primate survivorship.

SIRT3-dependent mitochondrial redox homeostasis mitigates CHK1 inhibition combined with gemcitabine treatment induced cardiotoxicity in hiPSC-CMs and mice - Jia-Wen Chen; Tian-Kai Shan; Tian-Wen Wei; Qi-Qi Jiang; Chong Du; Ling-Feng Gu; Tong-Tong Yang; Liu-Hua Zhou; Si-Bo Wang; Yu-Lin Bao; Hao Wang; Yong Ji; et al. (Archives of Toxicology, 2023)

Local temperature responses to actual land cover changes present significant latitudinal variability and asymmetry - Xiangyang Liu; Zhao-Liang Li; Yitao Li; Hua Wu; Chenghu Zhou; Menglin Si; Pei Leng; Si-Bo Duan; Peng Yang; Wenbin Wu; Ronglin Tang; Meng Liu; et al. (Science Bulletin, 2023)

Lindenane sesquiterpenoid dimers from Chloranthus holostegius with anti-neuroinflammatory activities in BV-2 microglia - Zhao-Chun Zhan; Yi-Ping Xia; Qing Tang; Hui-Hui Zhu; Jing-Yi Du; Jun-Xing Cai; Yan-Jun Chen; Zhong-Nan Wu; Yao-Lan Li; Neng-Hua Chen; Guo-Cai Wang; Yu-Bo Zhang (Phytochemistry, 2023)

Numerical simulation of flow instability induced by a fixed cylinder placed near a plane wall in oscillating flow - Zi-Fang Li; Jiang-Hua Li; Jian-Zhao Wu; Kai-Leong Chong; Bo-Fu Wang; Quan Zhou; Yu-Lu Liu (Ocean Engineering, 2023)

Self-similarity of sand bed scour by an oblique impinging plane jet under different Reynolds numbers - Jieyun Mao; Jin-Hua Si; Guidong Li; Bo Zhou; Xikun Wang (Ocean Engineering, 2023)

Contribution identification of hydrolyzed products of potassium ferrate on promoting short-chain fatty acids production from waste activated sludge - Cong-Cong Tang; Min Zhang; Bo Wang; Zheng-Shuo Zou; Xing-Ye Yao; Ai-Juan Zhou; Wenzong Liu; Yong-Xiang Ren; Zhi-Hua Li; Aijie Wang; Zhang-Wei He (Journal of Environmental Management, 2023)

Pyrolysis of waste printed circuit boards: Parametric effects on product distribution, characterization and gas emissions - Yunfeng Zhu; Bo Li; Yonggang Wei; Shiwei Zhou; Hua Wang (Process Safety and Environmental Protection, 2023)

Bimodal interferences of Pb(II) induced by parallel deposition in Pb(II)-Cu(II) electrochemical detections: Voltammetric signals analysis combined with numerical simulations on transient interfacial phenomena - Rui-Ze Xia; Xin Cai; Bo Liang; Hai-Hua Dai; Yang-Zhi Liu; Meng Yang; Shi-Hua Chen; Pei-Hua Li; Xing-Jiu Huang (Journal of Hazardous Materials, 2023)

Application of UPLC-Triple TOF-MS/MS metabolomics strategy to reveal the dynamic changes of triterpenoid saponins during the decocting process of Asian ginseng and American ginseng - Li-Hua Chen; You-Bo Zhang; Xiu-Wei Yang; Jing Xu; Zhao-Jing Wang; Yi-Zheng Sun; Wei Xu; Ying-Ping Wang (Food Chemistry, 2023)

N-doped carbon dots coupled with molecularly imprinted polymers as a fluorescent sensor for ultrasensitive detection of genistein in soya products - Yu-Zhen Zhang; Bo Zhang; Qing-Qing Chen; Lan Qin; Ya-Qi Hu; Chun-Hua Bai; Yi-Le Li; Bei Qin (Food Chemistry, 2023)

Feature Extraction with Multi-fractal Spectrum for Coal and Gangue Recognition Based on Texture Energy Field - Na Li; Si-bo Wu; Zhen-hua Yu; Xing-yu Gong (Natural Resources Research, 2023)

Revealing the solid-solution interface interference behaviors between Cu2+ and As(III) via partial peak area analysis of simulations and experiments - Bo Liang; Xiang-Yu Xiao; Zong-Yin Song; Yong-Yu Li; Xin Cai; Rui-Ze Xia; Shi-Hua Chen; Meng Yang; Pei-Hua Li; Chu-Hong Lin; Xing-Jiu Huang (Analytica Chimica Acta, 2023)

Expression and functional analysis of ace1 and ace2 reveal their differential roles in larval growth and insecticide sensitivity in Spodoptera frugiperda (J. E. Smith, 1797) - Jie Gao; Li-Feng Gong; Huan-Huan Wang; Rui Zhao; Xing Xiao; Xin-Yao Tian; Bo Li; Pei Liang; Xi-Wu Gao; Shao-Hua Gu (Journal of Pest Science, 2023)

Three new compounds isolated from the whole plants of Salsola collina pall - Wen-Zhi Wang; Zhao-Chun Zhan; Qing Tang; Ming Yan; Neng-Hua Chen; Hai-Yue Zhao; Hao-Yue Zhu; Huan-Qing Zhang; Zhong-Nan Wu; Hao-Yun Wang; Yu-Bo Zhang; Guo-Cai Wang; et al. (Natural Product Research, 2023)

Contrasting effects of different light regimes on the photoreactivities of allochthonous and autochthonous chromophoric dissolved organic matter - Wen-Zhuo Zhu; Shu-Heng Wang; De-Zhong Wang; Wei-Hua Feng; Bo Li; Hong-Hai Zhang (Chemosphere, 2023)

Anti-apoptotic effect of adrenomedullin gene delivery on Leydig cells by suppressing TGF-β1 via the Hippo signaling pathway - You-wen Luo; Xia-lian Zhu; Ming-yong Li; Jian-hua Zhou; Zhi-min Yang; Tao Tong; Bing-hai Chen; Song-lin Qin; Bo-long Liu; Wei Hu (Reproductive Toxicology, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Temperature dependent triplet-exciton relay from thermally activated delayed fluorescence (TADF) to self-sensitized triplet–triplet annihilation (TTA) of asymmetrical diphenylsulfone-based blue emitter - Jie Li; Yan Xia; Geng Li; Mingxing Chen; Jinhao Zhou; Wenjun Yan; Bo Zhao; Kunpeng Guo; Hua Wang (Chemical Engineering Journal, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

TMEM151A variants associated with paroxysmal kinesigenic dyskinesia - Hua lin Huang; Qing xia Zhang; Fei Huang; Xiao yan Long; Zhi Song; Bo Xiao; Guo liang Li; Cai yu Ma; Ding Liu (Human Genetics, 2023)

Alkylamides from Zanthoxylum armatum DC. and their neuroprotective activity - Qian-Nv Ye; Cheng-Bo Wang; Tian Chai; Jun Wang; Xian-Hua Meng; Xiao-Feng Shi; Jun-Li Yang (Phytochemistry, 2023)

Recovery of fluoride from spent cathode carbon block by combustion combined with water leaching process - Chenxi Zhu; Shiwei Zhou; Yonggang Wei; Bo Li; Hua Wang (Journal of Cleaner Production, 2023)

Purification and identification of xanthine oxidase inhibitory peptides from enzymatic hydrolysate of α-lactalbumin and bovine colostrum casein - Yi-Fang Gao; Meng-Qi Liu; Zhong-Han Li; Han-Lin Zhang; Jia-Qi Hao; Bo-Hao Liu; Xiao-Yan Li; Yu-Qi Yin; Xiao-Hui Wang; Qian Zhou; Di Xu; Bao-Ming Shi; et al. (Food Research International, 2023)

Source apportionment of nitrate in the Pearl River Estuary using δ15N and δ18O values and isotope mixing model - Ran Long; Fei Tian; Jian-hua Chen; Yan-bo Zhou; Xue-fei Li; Yi-tong Li; Hai-wei Tang; Hai-gang Chen (Marine Pollution Bulletin, 2023)

Zircon as a pathfinder for ore exploration - Huan Li; Xiao-Jun Hu; Safiyanu Muhammad Elatikpo; Jing-Hua Wu; Wei-Cheng Jiang; Wen-Bo Sun; Nuerkanati Madayipu (Journal of Geochemical Exploration, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

Pentacyclic triterpenoids from spikes of Prunella vulgaris L. with thyroid tumour cell cytostatic bioactivities - Xiu-Qin Zheng; Lei-Xin Song; Zhu-Zhen Han; Ying-Bo Yang; Yi Zhang; Li-Hua Gu; Li Yang; Gui-Xin Chou; Zheng-Tao Wang (Natural Product Research, 2023)

Recycling potential of waste printed circuit boards using pyrolysis: Status quo and perspectives - Yunfeng Zhu; Bo Li; Yonggang Wei; Shiwei Zhou; Hua Wang (Process Safety and Environmental Protection, 2023)

The effects of pulsed electric fields treatment on the structure and physicochemical properties of dialdehyde starch - Ying Li; Jin-Hua Wang; Yu Han; Fu-Hao Yue; Xin-An Zeng; Bo-Ru Chen; Man-Qin Zeng; Meng-Wai Woo; Zhong Han (Food Chemistry, 2023)

Interdecadal change in the linkage of early summer sea ice in the Barents Sea to the variability of West China Autumn Rain - Botao Zhou; Jin Qian; Yuepeng Hu; Hua Li; Tingting Han; Bo Sun (Atmospheric Research, 2023)

Transcriptome sequencing and metabolite analysis reveal the single and combined effects of microplastics and di-(2-ethylhexyl) phthalate on Peneaus vannamei - Qiang-Qiang Shi; Xiao-Qian Zhang; Ze-Ming Zhang; Ning-Bo Wang; Hua Liu; Rong-Rong Zhang; Ai-Li Sun; Jiong Chen; Xi-Zhi Shi (Science of The Total Environment, 2023)

Undescribed phloroglucinol derivatives with antiviral activities from Dryopteris atrata (Wall. Ex Kunze) Ching - Ji-hui Zhang; Jin-lin Chen; Wei-bin Xu; Yi-ping Xia; Hao-yue Zhu; Jing-hao Wang; Yao-lan Li; Guo-cai Wang; Yu-bo Zhang; Neng-hua Chen (Phytochemistry, 2023)

Magnetic ternary layered double hydroxides for efficient removal of 1-naphthalene acetic acid from waters: Adsorption behavior and mechanism - Ti-Bo Fang; Hua Xiao; Ling-Xi Zhao; Na Li; Ling-Yu Luan; Zhao-Xing Yan; Jin-Ming Lin; Ru-Song Zhao (Journal of Environmental Chemical Engineering, 2023)

Chlorination mechanism and kinetics of cathode materials for spent LiCoO2 batteries in the presence of graphite - Guorui Qu; Yonggang Wei; Bo Li; Hua Wang (Journal of Environmental Chemical Engineering, 2023)

Cellular and Molecular Mechanisms Underly the Combined Treatment of Fasudil and Bone Marrow Derived-Neuronal Stem Cells in a Parkinson’s Disease Mouse Model - Yu-Chen Yan; Yan-hua Li; Bao-Guo Xiao; Jian Wang; Jian-Ying Xi; Wen-Bo Yu (Molecular Neurobiology, 2023)

Cross-subject aesthetic preference recognition of Chinese dance posture using EEG - Jing Li; Shen-rui Wu; Xiang Zhang; Tian-jian Luo; Rui Li; Ying Zhao; Bo Liu; Hua Peng (Cognitive Neurodynamics, 2023)

A Cre knockin mouse reveals specific expression of Agouti gene in mesenchymal lineage cells in multiple organs and provides a unique tool for conditional gene targeting - Xing-Ru Shen; He-Li Zhang; Xu-Bo Zhao; Yang-Ge Wang; Xiao-Yang Tan; Lipeng Gao; Ruilin Sun; Xin-Hua Liao (Transgenic Research, 2023)

Influence of reservoir parameter variation on the multi-injection well model of the Voronoi fracture - Chang Shuai Shi; Shu Fan; Yan Xin Lv; Xiao Hua Zhu; Quan Gan; Hai Bo Li (Arabian Journal of Geosciences, 2023)

Explicit and size-adaptive PSO-based feature selection for classification - Litao Qu; Weibin He; Jianfei Li; Hua Zhang; Cheng Yang; Bo Xie (Swarm and Evolutionary Computation, 2023)

Estimation of mechanical and hydraulic parameters of bentonite-soil mixtures in oedometer condition with index properties - An Li; Wen-Bo Chen; Ze-Jian Chen; Pei-Chen Wu; Jian-Hua Yin; Chao Zhou (Bulletin of Engineering Geology and the Environment, 2023)

Distribution patterns of landslides triggered by the 2022 Ms 6.8 Luding earthquake, Sichuan, China - Jian-qiang Zhang; Zong-ji Yang; Qing-kai Meng; Jiao Wang; Kai-heng Hu; Yong-gang Ge; Feng-huan Su; Bo Zhao; Bo Zhang; Ning Jiang; Yu Huang; Zai-yang Ming; et al. (Journal of Mountain Science, 2023)

Risks of applying mobilising agents for remediation of arsenic-contaminated soils: Effects of dithionite–EDTA and citric acid on arsenic fractionation, leachability, oral bioavailability/bioaccessibility and speciation - Xiao-Chen Chen; Cong-Cong Yao; Ao Wang; Zeng-Di Zhang; Long-Zhao Chen; Jian-Yu Zhang; Xian-Hua Liu; Hong-Bo Li (Journal of Hazardous Materials, 2023)

Comprehensive application possibility: Construction hydrophilic, amphiphilic and hydrophobic system of modified zein by enzymatic or cysteine modification - An-Qi Zhang; Xiao-Yan Li; Bo-Hao Liu; Yu-Qi Yin; Han-Lin Zhang; Ying-Hua Zhang (Food Hydrocolloids, 2023)

Characteristics of groundwater microbial communities’ structure under the impact of elevated nitrate concentrations in north China plain - Bo Zhang; Zhi-Ling Li; Cai-Hua Bai; Jing-Lan Liu; Jun Nan; Di Cao; Li-Wei Li (Environmental Research, 2023)

Liquid flow and breakage behaviors of two liquid jets impacting on the wire mesh with different impinging angles - Zhong-Bo Sun; Hai-Long Liao; Li-Hua Wang; Lan Jiang; Xin Zhang; Bao-Ju Wang; Guang-Wen Chu; Yong Luo (Chemical Engineering Journal, 2023)

Pathology, Enzyme Activity and Immune Responses after Cryptocaryon irritans Infection of Golden Pompano Trachinotus ovatus (Linnaeus 1758) - Hua-Yang Guo; Wen-Fu Li; Ke-Cheng Zhu; Bao-Suo Liu; Nan Zhang; Bo Liu; Jing-Wen Yang; Dian-Chang Zhang (Journal of Marine Science and Engineering, 2023)
Golden pompano (Trachinotus ovatus) has become an economically important fish in China in the past decade. However, Cryptocaryon irritans, a parasitic ciliate, causes considerable economic losses in the mariculture of T. ovatus. To characterize the pathogenesis of C. irritans in T. ovatus, the pathological properties, immune-related enzyme activity and expression of the NEMO gene was analysed. The results from the histological sections showed that there was considerable metamorphosis and hyperplasia in the parasitized sites (skin) with leukocyte aggregation and mucous cell increases after C. irritans infection. Moreover, the activities of four enzymes, that is, alkaline phosphatase (AKP), acid phosphatase (ACP), superoxide dismutase (SOD) and lysozyme (LZM), were significantly increased in different tissues after C. irritans infection. Furthermore, the ORF of T. ovatus NF-kappa-B essential modulator (ToNEMO) measures 1650 bp, encoding 548 amino acids. The ToNEMO transcripts were universally expressed in all examined tissues, with higher levels being observed in the immune-relevant and central nervous tissues. The mRNA levels of ToNEMO after C. irritans infection were significantly increased in the gill, skin, liver, spleen and head kidney. These results suggested that ToNEMO might be involved in immune responses and helped to elucidate the physiological response after the C. irritans infection of fish.

A ca. 290 Ma hydrothermal calcite in Cambrian dolostone - Zhongwu Lan; Shitou Wu; Fangyue Wang; Bo Liu; Kaibo Shi; Jing Sun; Rong Cao; Xian-Hua Li (Marine and Petroleum Geology, 2023)

Coordination engineering strategy of iron single-atom catalysts boosts anti-Cu(II) interference detection of As(III) with a high sensitivity - Pei-Hua Li; Zong-Yin Song; Xiang-Yu Xiao; Bo Liang; Meng Yang; Shi-Hua Chen; Wen-Qing Liu; Xing-Jiu Huang (Journal of Hazardous Materials, 2023)

Performance characteristics of a two-stroke low speed engine applying ammonia/diesel dual direct injection strategy - Zhenxian Zhang; Wuqiang Long; Pengbo Dong; Hua Tian; Jiangping Tian; Bo Li; Yang Wang (Fuel, 2023)

Can sedentarization decrease the dependence of pastoral livelihoods on ecosystem services? - Xuhuan Dai; Bo Li; Hua Zheng; Yanzheng Yang; Zihan Yang; Chenchen Peng (Ecological Economics, 2023)

Research on Maneuverability Prediction of Double Waterjet Propulsion High Speed Planing Craft - Hua-Wei Sun; Jing-Lei Yang; Bo Liu; Hong-Wei Li; Jia-Feng Xiao; Han-Bing Sun (Journal of Marine Science and Engineering, 2022)
A mathematical model for predicting the maneuvering motion of a ship is constructed, using a planing craft with dual waterjet propulsion as the object of study. This model is based on the standard approach of the MMG (Maneuvering Modeling Group) and uses the Runge–Kutta algorithm to solve the differential equations. For the simulation of the turning and Z-shape maneuvering motion, the RANS equation is first solved using the program STAR-CCM + and then the PMM motion of the hull is simulated using the overlapping grid approach to derive the hydrodynamic derivative. The established method for predicting the ship’s maneuverability is feasible, as shown by the calculated results, which agree well with those obtained using data from the sea trials. This method was used to simulate the rudder rotation and Z-shape motion of the planing craft at medium and high speeds to predict the maneuverability index.

Ectopic expression of NAC transcription factor HaNAC3 from Haloxylon ammodendron increased abiotic stress resistance in tobacco - Xiashun Liu; Xingfeng Zong; Xia Wu; Hao Liu; Jvdong Han; Zhengpei Yao; Yanping Ren; Li Ma; Bo Wang; Hua Zhang (Planta, 2022)

Geomorphic and tectonic controls of landslides induced by the 2022 Luding earthquake - Bo Zhao; Kai-heng Hu; Zong-ji Yang; Qiao Liu; Qiang Zou; Hua-yong Chen; Bo Zhang; Wei-feng Zhang; Lei Zhu; Li-jun Su (Journal of Mountain Science, 2022)

First report of Bacillus velezensis JK-F2 for the biological control of crown gall in kiwifruit - Ting Ting Chen; Fei Ran; Jin Qiao Shi; Fei Xu Mo; Xian Hui Yin; Zhi Bo Zhao; Zhu Zhu Zhang; Wen Zhi Li; Li Nan He; You Hua Long (Journal of Plant Diseases and Protection, 2022)

Mapping the spatial distribution of fossil geothermal manifestations and assessment of geothermal potential of the Tangyin rift, Southeast of Taihang Mountain in China - Joshua Mahwa; Da-jiang Li; Jian-hua Ping; Wei Leng; Jia-bo Tang; Dong-yun Shao (Journal of Mountain Science, 2022)
The spatial prediction of geothermal sites along the southeast side of Taihang Mountain in the Tangyin rift is a critical goal in the development of renewable energy resources in cities such as Hebi in Henan province, which has significant potential for geothermal energy production due to the existence of deep faults and Cenozoic volcano. The study aimed to delineate areas with high geothermal manifestations for detailed geothermal exploration and well-test drilling. To define favorable zones for geothermal potentiality, multi-source datasets were chosen to generate evidence thematic layers that demonstrate the distribution of geothermal anomalies such as geologic maps, structural maps, Land Surface Temperature maps (LST), and hydrothermal mineral alterations maps. The remote sensing and Geographical Information System (GIS) approaches were integrated to map fossil geothermal manifestations and appraise the promising geothermal zones from Landsat 8 OLI/TIRS and Advanced Spaceborne Thermal Emission and Reflection Radiometer-Digital Elevation Model (ASTER-DEM) dataset using the Analytic Hierarchy Process (AHP), which is one of the Mult-criteria Decision Making methods. Results show LST values ranging from 22.6°C to 45.4°C, with the highest values found along the faults and volcanic areas. The hydrothermal alteration minerals discriminated from band ratios of 4/2, 6/5, and 6/7 for iron oxide, ferrous minerals, and clays reveal the presence of high amount of montmorillonite and illite minerals along the faults and volcanoes which are related to hot fluid circulation from subsurface. Structural analysis shows that the major structural trend follows the NNE Tangdong and Tangxi faults, with high density on the west side of the Tangxi fault where there is good exposure of outcrop but less fault density on the east side due to sedimentation in a low land which may conceal geological structures. Lastly, all the thematic layers of geothermal factors were reclassified, ranked, and integrated by the weight overlay logic model based on the influence of geothermal suitability to map potential areas for geothermal resources whereby 5 zones were obtained ranging from very poor to very good. The promising potential sites are mostly found along the highly deep structures of the major Tangxi fault crosscutting the permeable lithology of carbonate rocks and around the Hebi volcanoes. The distribution of hot springs and geothermal wells of the Hebi field were correlated and verified against the potential geothermal anomalies map. The overall integrated method proposes an advanced technique for designing the Tangyin rift’s exploration plan and development actions for geothermal resources utilization, which can be used for exploration of any unveiling geothermal potential sites.

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

LncDACH1 promotes mitochondrial oxidative stress of cardiomyocytes by interacting with sirtuin3 and aggravates diabetic cardiomyopathy - Qi Zhang; Danyang Li; Xue Dong; Xiaowen Zhang; Junwu Liu; Lili Peng; Bo Meng; Qi Hua; Xinyu Pei; Lu Zhao; Xiaoxi Hu; Yang Zhang; et al. (Science China Life Sciences, 2022)

Chrysomutanin and related meroterpenoids from a DES mutant of the marine-derived fungus Penicillium chrysogenum S-3-25 - Hua Qiao; Shu-Hua Zhang; Yuan Dong; Yu Yang; Rui Xu; Bo Chen; Yi Wang; Tian-Jiao Zhu; Cheng-Bin Cui; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2022)

Correction to: Downregulation of fibronectin 1 attenuates ATRA‑induced inhibition of cell migration and invasion in neuroblastoma cells - Xiaolin Tan; Wei Gong; Bo Chen; Baocheng Gong; Zhongyan Hua; Simeng Zhang; Yang Chen; Qi Li; Zhijie Li (Molecular and Cellular Biochemistry, 2022)

Coupling effect of biocementation-fiber reinforcement on mechanical behavior of calcareous sand for ocean engineering - Chao-Sheng Tang; Hao Li; Xiao-Hua Pan; Li-Yang Yin; Liang Cheng; Qing Cheng; Bo Liu; Bin Shi (Bulletin of Engineering Geology and the Environment, 2022)

A study of health management of LWD tool based on data-driven and model-driven - Hui Li; Zi-Hua He; Yu-ting Zhang; Jin Feng; Zun-Yi Jian; Yi-Bo Jiang (Acta Geophysica, 2022)

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

Yak Excreta Application Alter Nitrification by Regulating the Ammonia-Oxidizing Bacterial Communities in Wetland Soils - Li Chen; Rong Bo Zheng; Jun Qin Gao; Ming Hua Song; Xue Lian Guo (Journal of Soil Science and Plant Nutrition, 2021)

Seasonal prediction skills in the CAMS-CSM climate forecast system - Bo Liu; Jingzhi Su; Libin Ma; Yanli Tang; Xinyao Rong; Jian Li; Haoming Chen; Boqi Liu; Lijuan Hua; Renguang Wu (Climate Dynamics, 2021)

Two new isoquinoline alkaloids from the seeds of Nandina domestica - Juan Qin; Sheng-Yuan Zhang; Yu-Bo Zhang; Li-Feng Chen; Neng-Hua Chen; Zhong-Nan Wu; Ding Luo; Guo-Cai Wang; Yao-Lan Li (Natural Product Research, 2021)

Downregulation of fibronectin 1 attenuates ATRA-induced inhibition of cell migration and invasion in neuroblastoma cells - Xiaolin Tan; Wei Gong; Bo Chen; Baocheng Gong; Zhongyan Hua; Simeng Zhang; Yang Chen; Qi Li; Zhijie Li (Molecular and Cellular Biochemistry, 2021)

Apigenin Improves Hypertension and Cardiac Hypertrophy Through Modulating NADPH Oxidase-Dependent ROS Generation and Cytokines in Hypothalamic Paraventricular Nucleus - Hong-Li Gao; Xiao-Jing Yu; Han-Bo Hu; Qian-Wen Yang; Kai-Li Liu; Yan-Mei Chen; Yan Zhang; Dong-Dong Zhang; Hua Tian; Guo-Qing Zhu; Jie Qi; Yu-Ming Kang (Cardiovascular Toxicology, 2021)

CRWS-mountain Project: Coordinate remediation techniques and devices for water-soil pollution in mountain areas in China - Ling Song; Lei Li; Chao-jie Zhang; Li Huang; Jin-song Guo; Bo Zhu; Ming-hua Zhou (Journal of Mountain Science, 2021)

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Pathways of dissolved unreactive phosphorus loss under long-term crop straw and manure application - Keke Hua; Bo Zhu; Congcong Li (Nutrient Cycling in Agroecosystems, 2021)

Expressions and related mechanisms of miR-212 and KLF4 in rats with acute kidney injury - Xingguan Yang; Bo Li; Yu Guan; Hua-Mao Jiang (Molecular and Cellular Biochemistry, 2021)

NGF-Induced Nav1.7 Upregulation Contributes to Chronic Post-surgical Pain by Activating SGK1-Dependent Nedd4-2 Phosphorylation - Bao-Wen Liu; Jin Zhang; Yi-Shun Hong; Ning-Bo Li; Yi Liu; Mi Zhang; Wen-Yao Wu; Hua Zheng; Angelika Lampert; Xian-Wei Zhang (Molecular Neurobiology, 2021)

Arbuscular mycorrhizal colonization rate of an exotic plant, Galinsoga quadriradiata, in mountain ranges changes with altitude - Gang Liu; Rui-Ling Liu; Wen-Gang Zhang; Ying-Bo Yang; Xiao-Qiong Bi; Ming-Zhu Li; Xiao-Yan Chen; Hua Nie; Zhi-Hong Zhu (Mycorrhiza, 2021)

Alkaloids and phenylpropanoid from Rhizomes of Arundo donax L - Qing-Ru Liu; Juan Li; Xiao-Fang Zhao; Bo Xu; Xing-Hua Xiao; Jie Ren; Shun-Xiang Li (Natural Product Research, 2021)

The MYB transcription factor Baymax1 plays a critical role in rice male fertility - Xiao-Jiao Xiang; Lian-Ping Sun; Ping Yu; Zheng-Fu Yang; Pei-Pei Zhang; Ying-Xin Zhang; Wei-Xun Wu; Dai-Bo Chen; Xiao-Deng Zhan; Riaz-Muhammad Khan; Adil Abbas; Shi-Hua Cheng; et al. (Theoretical and Applied Genetics, 2021)

Genetic and epigenetic variations in barley (Hordeum vulgare L.) using SSR and MSAP approaches - Bo Li; Qiang Gong; Wei Hua; Gonghai Chen; Wenying Zhang; Yanhao Xu; Chengdao Li (Genetic Resources and Crop Evolution, 2021)

Transcriptome reveals genes involving in black skin color formation of ducks - Lei Wang; Hehe Liu; Bo Hu; Jiwei Hu; Hengyong Xu; Hua He; Chunchun Han; Bo Kang; Lili Bai; Rongping Zhang; Jiwen Wang; Shengqiang Hu; et al. (Genes & Genomics, 2021)

NUIST ESM v3 Data Submission to CMIP6 - Jian Cao; Libin Ma; Fei Liu; Jing Chai; Haikun Zhao; Qiong He; Bo Wang; Yan Bao; Juan Li; Young-min Yang; Hua Deng; Bin Wang (Advances in Atmospheric Sciences, 2021)
This paper introduces the experimental designs and outputs of the Diagnostic, Evaluation and Characterization of Klima (DECK), historical, Scenario Model Intercomparison Project (MIP), and Paleoclimate MIP (PMIP) experiments from the Nanjing University of Information Science and Technology Earth System Model version 3 (NESM3). Results show that NESM3 reasonably simulates the modern climate and the major internal modes of climate variability. In the Scenario MIP experiment, changes in the projected surface air temperature (SAT) show robust “Northern Hemisphere (NH) warmer than Southern Hemisphere (SH)” and “land warmer than ocean” patterns, as well as an El Niño-like warming over the tropical Pacific. Changes in the projected precipitation exhibit “NH wetter than SH” and “eastern hemisphere gets wetter and western hemisphere gets drier” patterns over the tropics. These precipitation patterns are driven by circulation changes owing to the inhomogeneous warming patterns. Two PMIP experiments show enlarged seasonal cycles of SAT and precipitation over the NH due to the seasonal redistribution of solar radiation. Changes in the climatological mean SAT, precipitation, and ENSO amplitudes are consistent with the results from PMIP4 models. The NESM3 outputs are available on the Earth System Grid Federation nodes for data users.

Cytotoxic triquinane-type sesquiterpenoids from the endophytic fungus Cerrena sp. A593 - Hong-Xin Liu; Hai-Bo Tan; Yu-Chan Chen; Sai-Ni Li; Hao-Hua Li; Wei-Min Zhang (Natural Product Research, 2020)

Privet golden leaves adapt unexpectedly well to light changes - Ming Yuan; Bo Huang; Li-Hua Dong; Qiao-Hong Han; Yong Yang; Chun-Bang Ding; Chao Hu; Yang-Er Chen; Zhong-Wei Zhang; Shu Yuan (Horticulture, Environment, and Biotechnology, 2020)

Genome-wide identification and expression analysis of the CLC superfamily genes in tea plants (Camellia sinensis) - Anqi Xing; Yuanchun Ma; Zichen Wu; Shouhua Nong; Jiaojiao Zhu; Hua Sun; Jing Tao; Bo Wen; Xujun Zhu; Wanping Fang; Xiaocheng Li; Yuhua Wang (Functional & Integrative Genomics, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

Efficacy of internet-based integrated intervention on depression and anxiety symptoms in patients with COVID-19 - Ning Wei; Bo-chao Huang; Shao-jia Lu; Jian-bo Hu; Xiao-yi Zhou; Chan-chan Hu; Jing-kai Chen; Jin-wen Huang; Shu-guang Li; Zheng Wang; Dan-dan Wang; Yi Xu; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Dialectical behavior therapy-based psychological intervention for woman in late pregnancy and early postpartum suffering from COVID-19: a case report - Jin-wen Huang; Xiao-yi Zhou; Shao-jia Lu; Yi Xu; Jian-bo Hu; Man-li Huang; Hua-fen Wang; Chan-chan Hu; Shu-guang Li; Jing-kai Chen; Zhong Wang; Shao-hua Hu; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Tracing solute sources and carbon dynamics under various hydrological conditions in a karst river in southwestern China - Jing Liu; Bo Chen; Zhu-Yan Xu; Yuan Wei; Zhi-Hua Su; Rui Yang; Yong-Xue Ji; Xiao-Dan Wang; Li-Li Zhang; Ning An; Fei Yang (Environmental Science and Pollution Research, 2020)

Drought sensitivity of aboveground productivity in Leymus chinensis meadow steppe depends on drought timing - Bo Meng; Baoku Shi; Shangzhi Zhong; Hua Chai; Shuixiu Li; Yunbo Wang; Hugh A. L. Henry; Jian-Ying Ma; Wei Sun (Oecologia, 2019)

Two new labdane diterpenoids from aerial parts of Leonurus japonicus and their anti-inflammatory activity - Yu-Mei Hu; Wen-Jun Liu; Meng-Xuan Li; Hai-Bo Li; Tao Jiang; Ning-Bo Cheng; Wen-Zhe Huang; Zhen-Zhong Wang; Hua-Xu Zhu; Wei Xiao (Natural Product Research, 2019)

Isolation and identification of new prenylated acetophenone derivatives from Acronychia oligophlebia - Qian-Wen Niu; Neng-Hua Chen; Zhong-Nan Wu; Ding Luo; Ying-Ying Li; Yu-Bo Zhang; Qing-Guo Li; Yao-Lan Li; Guo-Cai Wang (Natural Product Research, 2019)

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

Half-dose ticagrelor versus high-dose clopidogrel in reducing platelet reactivity in acute coronary syndrome patients with high on-clopidogrel platelet reactivity (divide study) - Guang Zhong Liu; Song Zhang; Dang Hui Sun; Jing Shi; Wan Lan Bo; Wen Nan Wang; Chong Yang Zhang; Zhong Hua Wang; Wei Feng; Mei Jiao He; Yuan Yuan Liu; Shuang Li; et al. (European Journal of Clinical Pharmacology, 2019)

Upregulation of phosphoinositide 3-kinase prevents sunitinib-induced cardiotoxicity in vitro and in vivo - Congxin Li; Ruya Zou; Hua Zhang; Yuhong Wang; Bo Qiu; Suhua Qiu; Wei Wang; Yanfang Xu (Archives of Toxicology, 2019)

Mitochondrial Gene Heterogeneity and Population Genetics of Haemaphysalis longicornis (Acari: Ixodidae) in China - Zhong-Bo Li; Yi-Tian Fu; Tian-Yin Cheng; Guo-Min Yao; Qiang-Hong Hou; Fen Li; Yu Zhao; Feng-Cai Zou; Guo-Hua Liu (Acta Parasitologica, 2019)

Novel hepacivirus in Asian house shrew, China - Hua Guo; Chunlin Cai; Bo Wang; Fei Zhuo; Rendi Jiang; Ning Wang; Bei Li; Wei Zhang; Yan Zhu; Yi Fan; Wushen Chen; Weihong Chen; et al. (Science China Life Sciences, 2019)

Analysis of genetic variation of porcine circovirus type 2 within pig populations in central China - Peng-Li Xu; Yu Zhao; Hui-Hua Zheng; Run-Bo Tian; Hao-Ying Han; Hong-Ying Chen; Lan-Lan Zheng (Archives of Virology, 2019)

An H-ferritin from the hydrothermal vent shrimp Rimicaris exoculata and its potential role in iron metabolism - Xiao-Li Liu; Sen Ye; Hua-Wei Li; Bo Lu; Yan-Qin Yu; Yu-Peng Fan; Wei-Jun Yang; Jin-Shu Yang (BioMetals, 2019)

A remote sensing method for retrieving land surface emissivity and temperature in cloudy areas: a case study over South China - Fang-Cheng Zhou; Zhao-Liang Li; Hua Wu; Si-Bo Duan; Xiaoning Song; Guangjian Yan (International Journal of Remote Sensing, 2019)

Invasive Spartina alterniflora exhibits increased resistance but decreased tolerance to a generalist insect in China - Rui-Ting Ju; Ding Ma; Evan Siemann; Xiang Liu; Ji-Hua Wu; Bo Li (Journal of Pest Science, 2019)

Role of prefrontal cortex in the extinction of drug memories - Wen-Hua Zhang; Ke-Xin Cao; Zeng-Bo Ding; Jian-Li Yang; Bing-Xing Pan; Yan-Xue Xue (Psychopharmacology, 2019)

The Influence of Cellulosic Polymer’s Variables on Dissolution/Solubility of Amorphous Felodipine and Crystallization Inhibition from a Supersaturated State - Nian-Qiu Shi; Ying Jin; Yong Zhang; Xiao-Xia Che; Xiao Xiao; Gui-Hua Cui; Yu-Zhou Chen; Bo Feng; Zheng-Qiang Li; Xian-Rong Qi (AAPS PharmSciTech, 2019)

Enzymatic gene expression by Pleurotus tuoliensis (Bailinggu): differential regulation under low temperature induction conditions - Shuang Hua; Bo Zhang; Yongping Fu; Bao Qi; Yanshuang Li; Fenghua Tian; Yu Li (World Journal of Microbiology and Biotechnology, 2018)

Acute effect of fine and coarse particular matter on cardiovascular visits in Ningbo, China - Pei-wen Zheng; Peng Shen; Zhen-hua Ye; Zhen-yu Zhang; Peng-fei Chai; Die Li; Ming-juan Jin; Meng-Ling Tang; Huai-chu Lu; Hong-bo Lin; Jian-bing Wang; Kun Chen (Environmental Science and Pollution Research, 2018)

Secondary metabolites from the Colletotrichum gloeosporioides A12, an endophytic fungus derived from Aquilaria sinensis - Hong-Xin Liu; Hai-Bo Tan; Yu-Chan Chen; Sai-Ni Li; Hao-Hua Li; Wei-Min Zhang (Natural Product Research, 2018)

The genesis of Mo-Cu deposits and mafic igneous rocks in the Senj area, Alborz magmatic belt, Iran - Ghasem Nabatian; Xian-Hua Li; Bo Wan; Maryam Honarmand (Mineralogy and Petrology, 2018)

Endophytic Fungal strains Specifically Modified the Biochemical Status of Grape Cells - Ming-Zhi Yang; Li-Hua Huang; Xiu-Jin Ao; An-Yun Ren; Ming-Quan Yuan; Han-Bo Zhang (Journal of Plant Biology, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

New pyridocarbazole alkaloids from Strychnos nitida - Wei Li; Gui-Hua Tang; Lin Chen; Ya-Qi Tang; You-Kai Xu; Bo Liu; Sheng Yin (Natural Product Research, 2018)

Bioaccumulation and Distribution of Hexabromocyclododecane Isomers in Duck Tissues - Wei Xia; Jianmei Wang; Hua Yang; Hu Zhang; Bo Yang; Yinhuan Zeng; Jie Xu; Zuguang Li; Mingrong Qian (Bulletin of Environmental Contamination and Toxicology, 2018)

Isolation and characterization of 33 EST-SNP markers in Schizothorax prenanti - Jian Zhou; Bo Zhou; Qiang Li; Lu Zhang; Jun Du; Hua Ye (Conservation Genetics Resources, 2018)

Genome-wide analysis and expression profiling of the HMA gene family in Brassica napus under cd stress - Nannan Li; Hua Xiao; Juanjuan Sun; Shufeng Wang; Jingchao Wang; Peng Chang; Xinbin Zhou; Bo Lei; Kun Lu; Feng Luo; Xiaojun Shi; Jiana Li (Plant and Soil, 2018)

Validation of reference genes for accurate normalization of gene expression with quantitative real-time PCR in Haloxylon ammodendron under different abiotic stresses - Bo Wang; Huihui Du; Zhengpei Yao; Cai Ren; Li Ma; Jiao Wang; Hua Zhang; Hao Ma (Physiology and Molecular Biology of Plants, 2018)

Alpha Lipoamide Ameliorates Motor Deficits and Mitochondrial Dynamics in the Parkinson’s Disease Model Induced by 6-Hydroxydopamine - Bo Zhou; Min Wen; Xin Lin; Yun-Hua Chen; Yun Gou; Yong Li; Yi Zhang; Hong-Wei Li; Lei Tang (Neurotoxicity Research, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Fine crustal and uppermost mantle S-wave velocity structure beneath the Tengchong volcanic area inferred from receiver function and surface-wave dispersion: constraints on magma chamber distribution - Mengkui Li; Shuangxi Zhang; Tengfei Wu; Yujin Hua; Bo Zhang (Bulletin of Volcanology, 2018)

Compounds with inhibitory activity on peristalsis from the seeds of Holarrhena antidysenterica - Hai-Hua Xie; Jian Su; Xiao-Lei Ge; Ting-Ting Dong; Xin Li; Hui-Min Wen; Bo-Hang Sun (Natural Product Research, 2018)

Development and validation of SSR markers based on transcriptome sequencing of Casuarina equisetifolia - Nan Li; Yong-Qi Zheng; Hong-Mei Ding; He-Peng Li; Hua-Zheng Peng; Bo Jiang; Hai-Bo Li (Trees, 2018)

Molecular characterization of hard tick Haemaphysalis longicornis from China by sequences of the internal transcribed spacers of ribosomal DNA - Zhong-Bo Li; Guo-Hua Liu; Tian-Yin Cheng (Experimental and Applied Acarology, 2018)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Taxanes from Taxus wallichiana var. mairei cultivated in the southern area of the Yangtze River in China - Bo-Shu Lun; Li-Wei Shao; Yong Wang; Cong-Cong Li; Hua Yu; Chun-Hua Wang; Yan Zhu (Natural Product Research, 2017)

Fasudil Enhances Therapeutic Efficacy of Neural Stem Cells in the Mouse Model of MPTP-Induced Parkinson’s Disease - Yan-Hua Li; Jing-Wen Yu; Jian-Yin Xi; Wen-Bo Yu; Jian-Chun Liu; Qing Wang; Li-Juan Song; Ling Feng; Ya-Ping Yan; Guang-Xian Zhang; Bao-Guo Xiao; Cun-gen Ma (Molecular Neurobiology, 2017)

Clinical efficacy of percutaneous cryoablation combined with allogenic NK cell immunotherapy for advanced non-small cell lung cancer - Mao Lin; Shu-Zhen Liang; Xiao-Hua Wang; Ying-Qing Liang; Ming-Jie Zhang; Li-Zhi Niu; Ji-Bing Chen; Hai-Bo Li; Ke-Cheng Xu (Immunologic Research, 2017)

Association of GWAS-Reported Variant rs11196288 near HABP2 with Ischemic Stroke in Chinese Han Population - Shao-hua Li; Chang-he Shi; Yu-sheng Li; Fang Li; Mi-bo Tang; Xin-jing Liu; Shuo Zhang; Zhi-lei Wang; Bo Song; Yu-ming Xu (Journal of Molecular Neuroscience, 2017)

Three new diterpenoids from Croton laui Merr. et Metc - Li Yang; Zhong-Nan Wu; Yu-Bo Zhang; Neng-Hua Chen; Ling Zhuang; Yao-Lan Li; Guo-Cai Wang (Natural Product Research, 2017)

RETRACTED ARTICLE: Role of Glibenclamide in Brain Injury After Intracerebral Hemorrhage - Bing Jiang; Lin Li; Qianwei Chen; Yihao Tao; Liming Yang; Bo Zhang; John H. Zhang; Hua Feng; Zhi Chen; Jun Tang; Gang Zhu (Translational Stroke Research, 2017)

Transcriptomic analysis of Casuarina equisetifolia L. in responses to cold stress - Hai-Bo Li; Nan Li; Shao-Zong Yang; Hua-Zheng Peng; Li-Ling Wang; Yong Wang; Xiao-Mian Zhang; Zhi-Hui Gao (Tree Genetics & Genomes, 2017)

Mice lacking myotubularin-related protein 14 show accelerated high-fat diet-induced lipid accumulation and inflammation - Lv Yin; Peng Yong-bo; Yu Meng-Fei; Chen Weiwei; Zhao Ping; Xue Lu; Ma Li-Qun; Cai Congli; Liu Qing-hua; Shen Jinhua (Journal of Physiology and Biochemistry, 2017)

Genetic variation in mitochondrial genes of the tick Haemaphysalis flava collected from wild hedgehogs in China - Zhong-Bo Li; Tian-Yin Cheng; Xing-Li Xu; Lu-Lin Song; Guo-Hua Liu (Experimental and Applied Acarology, 2017)

Optimized culture medium for the production of flavonoids from Orostachys cartilaginea V.N. Boriss. callus cultures - Wan Bo Zhang; Xuan Chun Piao; Jin Rong Li; Ying Hua Jin; Mei Lan Lian (In Vitro Cellular & Developmental Biology - Plant, 2017)

Hierarchy evaluation of water resources vulnerability under climate change in Beijing, China - Xiao-Hua Yang; Bo-Yang Sun; Jian Zhang; Mei-Shui Li; Jun He; Yi-Ming Wei; Yu-Qi Li (Natural Hazards, 2016)

Genome-wide study refines the quantitative trait locus for number of ribs in a Large White × Minzhu intercross pig population and reveals a new candidate gene - Long-Chao Zhang; Jing-Wei Yue; Lei Pu; Li-Gang Wang; Xin Liu; Jing Liang; Hua Yan; Ke-Bin Zhao; Na Li; Hui-Bi Shi; Yue-Bo Zhang; Li-Xian Wang (Molecular Genetics and Genomics, 2016)

Netrin-1 Contributes to Myelinated Afferent Fiber Sprouting and Neuropathic Pain - Cai-Hua Wu; Xiao-Cui Yuan; Fang Gao; Hong-Ping Li; Jie Cao; Yan-Shen Liu; Wei Yu; Bo Tian; Xian-Fang Meng; Jing Shi; Hui-Lin Pan; Man Li (Molecular Neurobiology, 2016)

Estimating cropland carbon mitigation potentials in China affected by three improved cropland practices - Fei Lun; Josep G. Canadell; Lu He; Bo Yang; Mou-cheng Liu; Zheng Yuan; Mi Tian; Jun-guo Liu; Wen-hua Li (Journal of Mountain Science, 2016)

Transcriptome analysis reveals translational regulation in barley microspore-derived embryogenic callus under salt stress - Cheng-hong Liu; Rui-ju Lu; Gui-mei Guo; Ting He; Ying-bo Li; Hong-wei Xu; Run-hong Gao; Zhi-wei Chen; Jian-hua Huang (Plant Cell Reports, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Genetic polymorphism analyses of a novel panel of 19 X-STR loci in the Chinese Uygur ethnic minority - Yu-xin Guo; Jian-gang Chen; Yan Wang; Jiang-wei Yan; Jing Chen; Tian-hua Yao; Li-ping Zhang; Guang Yang; Hao-tian Meng; Yu-dang Zhang; Ting Mei; Yao-shun Liu; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

MicroRNA-25 Negatively Regulates Cerebral Ischemia/Reperfusion Injury-Induced Cell Apoptosis Through Fas/FasL Pathway - Jun-feng Zhang; Li-li Shi; Li Zhang; Zhao-hua Zhao; Fei Liang; Xi Xu; Ling-yu Zhao; Peng-bo Yang; Jian-shui Zhang; Ying-fang Tian (Journal of Molecular Neuroscience, 2016)

Functional polymorphisms in the gene encoding macrophage migration inhibitory factor (MIF) are associated with active pulmonary tuberculosis - Shou-Gang Kuai; Qin-Fang Ou; De-Hong You; Zhong-Bo Shang; Jun Wang; Jun Liu; Xi-Ke Zhou; Hao Pei; Li-Hua Huang (Infectious Diseases, 2016)

The SIRT1 inhibitor, nicotinamide, inhibits hepatitis B virus replication in vitro and in vivo - Wan-Yu Li; Ji-Hua Ren; Na-Na Tao; Long-Kuan Ran; Xiang Chen; Hong-Zhong Zhou; Bo Liu; Xiao-Song Li; Ai-Long Huang; Juan Chen (Archives of Virology, 2016)

JA, a new type of polyunsaturated fatty acid isolated from Juglans mandshurica Maxim, limits the survival and induces apoptosis of heptocarcinoma cells - Xiu-Li Gao; Hua Lin; Wei Zhao; Ya-Qin Hou; Yong-Li Bao; Zhen-Bo Song; Lu-Guo Sun; Shang-Yi Tian; Biao Liu; Yu-Xin Li (Apoptosis, 2016)

The microRNA167 controls somatic embryogenesis in Arabidopsis through regulating its target genes ARF6 and ARF8 - Ying Hua Su; Yu Bo Liu; Chao Zhou; Xiao Ming Li; Xian Sheng Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Programmed Death Ligand-1 on Microglia Regulates Th1 Differentiation via Nitric Oxide in Experimental Autoimmune Encephalomyelitis - Jingxia Hu; Hao He; Zhengang Yang; Guangming Zhu; Li Kang; Xiuli Jing; Hai Lu; Wengang Song; Bo Bai; Hua Tang (Neuroscience Bulletin, 2016)

Expression of Shewanella frigidimarina fatty acid metabolic genes in E. coli by CRISPR/cas9-coupled lambda Red recombineering - Jun Xia; Ling Wang; Jian-bo Zhu; Cheng-jun Sun; Ming-gang Zheng; Li Zheng; Ying-hua Lou; Lei Shi (Biotechnology Letters, 2016)

Decreased Zn2+ Influx Underlies the Protective Role of Hypoxia in Rat Nucleus Pulposus Cells - Yin Xiao-Fan; Jiang Li-Bo; Ma Yi-Qun; Xu Jun; Gu Hui-Jie; Wu Xu-Hua; Li Xi-Lei; Dong Jian (Biological Trace Element Research, 2015)

Validation of a practical normalized soil moisture model with in situ measurements in humid and semi-arid regions - Dianjun Zhang; Zhao-Liang Li; Ronglin Tang; Bo-Hui Tang; Hua Wu; Jing Lu; Kun Shao (International Journal of Remote Sensing, 2015)

A three-channel algorithm for retrieving night-time land surface temperature from MODIS data under thin cirrus clouds - Xiwei Fan; Bo-Hui Tang; Hua Wu; Guangjian Yan; Zhao-Liang Li (International Journal of Remote Sensing, 2015)

Integrating two layers of soil moisture parameters into the MOD16 algorithm to improve evapotranspiration estimations - Su-Chuang Di; Zhao-Liang Li; Ronglin Tang; Hua Wu; Bo-Hui Tang; Jing Lu (International Journal of Remote Sensing, 2015)

Effects of cold acclimation on sugar metabolism and sugar-related gene expression in tea plant during the winter season - Chuan Yue; Hong-Li Cao; Lu Wang; Yan-Hua Zhou; Yu-Ting Huang; Xin-Yuan Hao; Yu-Chun Wang; Bo Wang; Ya-Jun Yang; Xin-Chao Wang (Plant Molecular Biology, 2015)

Patients with type 2 diabetes exhibit cognitive impairment with changes of metabolite concentration in the left hippocampus - Yue Wang; Xiao-yun Xu; Chun-hua Feng; Yuan-ling Li; Xia Ge; Gen-lin Zong; Yi-bin Wang; Bo Feng; Peng Zhang (Metabolic Brain Disease, 2015)

Proteomics analysis for enhanced lipid accumulation in oleaginous Chlorella vulgaris under a heterotrophic-Na+ induction two-step regime - Yuqin Li; Jinxiu Mu; Di Chen; Hua Xu; Fangxin Han; Bo Feng; Hongyan Zeng (Biotechnology Letters, 2015)

Isolation and characterization of pyrroline-5-carboxylate synthetase gene from perennial ryegrass (Lolium perenne L.) - Li Cao; Lei Han; Hua-li Zhang; Hai-bo Xin; Muhammad Imtiaz; Ming-Fang Yi; Zhen-Yuan Sun; Guan-Sheng Ju; Yong-Qiang Qian; Jun-Xiang Liu (Acta Physiologiae Plantarum, 2015)

Morphological changes in gray matter volume correlate with catechol-O-methyl transferase gene Val158Met polymorphism in first-episode treatment-naïve patients with schizophrenia - Ming-Li Li; Bo Xiang; Yin-Fei Li; Xun Hu; Qiang Wang; Wan-Jun Guo; Wei Lei; Chao-Hua Huang; Lian-Sheng Zhao; Na Li; Hong-Yan Ren; Hui-Yao Wang; et al. (Neuroscience Bulletin, 2015)

A new antioxidant flavone glycoside from Scutellaria baicalensis Georgi - Meng-Hua Wang; Lin-Zhen Li; Jian-Bo Sun; Fei-Hua Wu; Jing-Yu Liang (Natural Product Research, 2014)

Accumulation of FLT3+ CD11c+ dendritic cells in psoriatic lesions and the anti-psoriatic effect of a selective FLT3 inhibitor - Heng-Xiu Yan; Wei-Wei Li; Yan Zhang; Xia-Wei Wei; Li-Xin Fu; Guo-Bo Shen; Tao Yin; Xiu-Ying Li; Hua-Shan Shi; Yang Wan; Qing-Yin Zhang; Jiong Li; et al. (Immunologic Research, 2014)

Expression, cloning, and IgE-binding of the full-length dust mite allergen Der f 8 - Yu-bao Cui; Ying Zhou; Nan Wang; Fei-xiang Teng; Li-li Yu; Yong-hua Bian; Jin-xia Song; Li Yang; Cheng-bo Zhang (Immunologic Research, 2014)

Flavonoids and other constituents from Aletris spicata and their chemotaxonomic significance - Lin-Zhen Li; Meng-Hua Wang; Jian-Bo Sun; Jing-Yu Liang (Natural Product Research, 2014)

Bioactive Equivalence of Combinatorial Components Identified in Screening of an Herbal Medicine - Peng Liu; Hua Yang; Fang Long; Hai-Ping Hao; Xiaojun Xu; Ying Liu; Xiao-Wei Shi; Dan-Dan Zhang; Hao-Chuan Zheng; Qian-Ying Wen; Wen-Wen Li; Hui Ji; et al. (Pharmaceutical Research, 2014)

Molecular cloning and dimorphic expression of growth hormone (gh) in female and male spotted scat Scatophagus argus - Si-Ping Deng; Bo Wu; Chun-Hua Zhu; Guang-Li Li (Fisheries Science, 2014)

The differentiation and development of pistils of hermaphrodites and pistillodes of males in androdioecious Osmanthus fragrans L. and implications for the evolution to androdioecy - Yi-Chun Xu; Li-Hua Zhou; Shao-Qing Hu; Ri-Ming Hao; Chong-jing Huang; Hong-Bo Zhao (Plant Systematics and Evolution, 2014)

EGF Enhances ADSCs Secretion via ERK and JNK Pathways - Qiang Li; Pei-hua Li; Dian-ju Hou; Ai-jun Zhang; Chang-bo Tao; Xue-yang Li; Pei-sheng Jin (Cell Biochemistry and Biophysics, 2014)

Primordial follicle assembly was regulated by notch signaling pathway in the mice - Chun-Lei Chen; Xia-Fei Fu; Lin-Qing Wang; Jun-Jie Wang; Hua-Gang Ma; Shun-Feng Cheng; Zhu-Mei Hou; Jin-Mei Ma; Guo-Bo Quan; Wei Shen; Lan Li (Molecular Biology Reports, 2014)

Neuroprotective Effects of Bis(7)-tacrine in a Rat Model of Pressure-Induced Retinal Ischemia - Jing-bo Li; Zhi-gang Lu; Li Xu; Qi Wang; Zu-hai Zhang; Jia-hua Fang (Cell Biochemistry and Biophysics, 2014)

A monocarbonyl analogue of curcumin, 1,5-bis(3-hydroxyphenyl)-1,4-pentadiene-3-one (Ca 37), exhibits potent growth suppressive activity and enhances the inhibitory effect of curcumin on human prostate cancer cells - Cheng Luo; Yan Li; Bo Zhou; Liang Yang; Hua Li; Zhihui Feng; Yuan Li; Jiangang Long; Jiankang Liu (Apoptosis, 2014)

Shapinggou: the largest Climax-type porphyry Mo deposit in China - Hong Zhang; Cong-Ying Li; Xiao-Yong Yang; Ya-Li Sun; Jiang-Hong Deng; Hua-Ying Liang; Rui-Long Wang; Bo-Hua Wang; Yu-Xian Wang; Wei-Dong Sun (International Geology Review, 2014)

Assessment of wheat variety stability using SSR markers - Li Xin Wang; Hong Bo Li; Tie Cheng Gu; Li Hua Liu; Bin Shuang Pang; Jun Qiu; Chang Ping Zhao (Euphytica, 2014)

Xanthoceraside attenuates tau hyperphosphorylation and cognitive deficits in intracerebroventricular-streptozotocin injected rats - Peng Liu; Li-Bo Zou; Li-Hua Wang; Qing Jiao; Tian-Yan Chi; Xue-Fei Ji; Ge Jin (Psychopharmacology, 2014)

The Analysis of Turbulence Intensity and Reynolds Shear Stress in Wall-Bounded Turbulent Flows at High Reynolds Numbers - Hong-You Liu; Tian-Li Bo; Guo-Hua Wang; Xiao-Jing Zheng (Boundary-Layer Meteorology, 2014)

Human umbilical cord-derived MSC culture: the replacement of animal sera with human cord blood plasma - Yan Ding; Hua Yang; Jing Bo Feng; Ying Qiu; Dong Sheng Li; Yi Zeng (In Vitro Cellular & Developmental Biology - Animal, 2013)

Application of Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration in the Management of Mediastinal and Hilar Lymphadenopathy Without Intrapulmonary Mass: Experience from the Largest Cancer Center of Southern China - Guang-yu Luo; Pei-qiang Cai; Jie-hua He; Jian-jun Li; Yin Li; Hong-bo Shan; Rong Zhang; Xiao-yan Gao; Xiang-ming Lao; Guo-liang Xu (Cell Biochemistry and Biophysics, 2013)

Factors influencing the grazing management styles of settled herders: a case study of Nagqu County, Tibetan Plateau, China - Xiao-bo Hua; Jian-zhong Yan; Xiang Liu; Ying-ying Wu; Lin-shan Liu; Yi-li Zhang (Journal of Mountain Science, 2013)

Estimating net surface longwave radiation from net surface shortwave radiation for cloudy skies - Xiao-Ming Zhou; Bo-Hui Tang; Hua Wu; Zhao-Liang Li (International Journal of Remote Sensing, 2013)

Partial least squares based identification of Duchenne muscular dystrophy specific genes - Hui-bo An; Hua-cheng Zheng; Li Zhang; Lin Ma; Zheng-yan Liu (Journal of Zhejiang University-SCIENCE B, 2013)

Estradiol inhibits osteoblast apoptosis via promotion of autophagy through the ER–ERK–mTOR pathway - Yue-Hua Yang; Ke Chen; Bo Li; Jiang-Wei Chen; Xin-Feng Zheng; Yu-Ren Wang; Sheng-Dan Jiang; Lei-Sheng Jiang (Apoptosis, 2013)

The first complete genomic characterization of an Amur virus isolate from China - Yu Zhang; Bo-Hua Liu; Fang Lin; Yong-Guo Zhang; Bing-Yin Si; Xiao-Ping Kang; Yi Hu; Jing Li; Xiao-Yan Wu; Yu-Chang Li; Qing-Yu Zhu; Yin-Hui Yang (Archives of Virology, 2013)

Development and evaluation of multi-genotype varieties of rice derived from MAGIC lines - Xiao-Fang Li; Zhi-Xia Liu; Dong-Bo Lu; Yan-Zhuo Liu; Xing-Xue Mao; Zhi-Xin Li; Hua-Jun Li (Euphytica, 2013)

A generalized split-window algorithm for land surface temperature estimation from MSG-2/SEVIRI data - Caixia Gao; Bo-Hui Tang; Hua Wu; Xiaoguang Jiang; Zhao-Liang Li (International Journal of Remote Sensing, 2013)

Activation of Akt and cardioprotection against reperfusion injury are maximal with only five minutes of sevoflurane postconditioning in isolated rat hearts - Yuan-yuan Yao; Man-hua Zhu; Feng-jiang Zhang; Chuan-yun Wen; Lei-lei Ma; Wen-na Wang; Can-can Wang; Xian-bao Liu; Li-na Yu; Ling-bo Qian; Jian-an Wang; Min Yan (Journal of Zhejiang University-SCIENCE B, 2013)

Impact of nonlinearity and discontinuity on the spatial scaling effects of the leaf area index retrieved from remotely sensed data - Hua Wu; Bo-Hui Tang; Zhao-Liang Li (International Journal of Remote Sensing, 2013)

Land surface emissivity retrieval from satellite data - Zhao-Liang Li; Hua Wu; Ning Wang; Shi Qiu; José A. Sobrino; Zhengming Wan; Bo-Hui Tang; Guangjian Yan (International Journal of Remote Sensing, 2013)

Erratum to: Altered regional homogeneity in Posttraumatic Stress Disorder: a resting state functional magnetic resonance imaging study - Yan Yin; Changfeng Jin; Lisa T. Eyler; Hua Jin; Xiaolei Hu; Lian Duan; Huirong Zheng; Bo Feng; Xuanyin Huang; Baoci Shan; Qiyong Gong; Lingjiang Li (Neuroscience Bulletin, 2013)

Comparative transcriptome analysis of tobacco (Nicotiana tabacum) leaves to identify aroma compound-related genes expressed in different cultivated regions - Bo Lei; Xue-Hua Zhao; Kai Zhang; Jie Zhang; Wei Ren; Zhu Ren; Yi Chen; Hui-Na Zhao; Wen-Jie Pan; Wei Chen; Hong-Xun Li; Wen-Ya Deng; et al. (Molecular Biology Reports, 2013)

Optimization of fermentation process for the production of intracellular polysaccharide from Paecilomyces cicadae and the immuno-stimulating activity of intracellular polysaccharide - Jun-Wen Cheng; Yan-Bin Wang; Liang He; Hua Qian; Li-Zhong Fu; Hai-Bo Li (World Journal of Microbiology and Biotechnology, 2012)

Methods to measure and analyze ciliary beat activity: Ca2+ influx-mediated cilia mechanosensitivity - Wen-Er Li; Weiwei Chen; Yun-Fei Ma; Qing-Rong Tuo; Xiao-Jing Luo; Ting Zhang; Wen-Bo Sai; Jing Liu; Jinhua Shen; Zhi-Gang Liu; Yun-Min Zheng; Yong-Xiao Wang; et al. (Pflügers Archiv - European Journal of Physiology, 2012)

Numerical modeling of PP- and PS-wave azimuthal anisotropy in HTI media - Zhong-Ping Qian; Shao-Hua Zhang; Bo Zhao; Na Lei; Xiang-Yang Li (Applied Geophysics, 2012)

Altered regional homogeneity in post-traumatic stress disorder: a restingstate functional magnetic resonance imaging study - Yan Yin; Changfeng Jin; Lisa T. Eyler; Hua Jin; Xiaolei Hu; Lian Duan; Huirong Zheng; Bo Feng; Xuanyin Huang; Baoci Shan; Qiyong Gong; Lingjiang Li (Neuroscience Bulletin, 2012)

Sequence and phylogenetic analysis of H7N3 avian influenza viruses isolated from poultry in China in 2011 - Wu Hai-bo; Lu Ru-feng; Wo En-kang; You Jin-biao; Wang Yi-ting; Wang Qiao-gang; Xu Li-hua; Wu Nan-ping; Guo Chao-tan (Archives of Virology, 2012)

The expression of pentraxin 3 and tumor necrosis factor-alpha is increased in preeclamptic placental tissue and maternal serum - Ping Zhou; Xin Luo; Hong-bo Qi; Wen-jun Zong; Hua Zhang; Dan-dan Liu; Qing-shu Li (Inflammation Research, 2012)

Effects of fertilization and drought stress on tannin biosynthesis of Casuarina equisetifolia seedlings branchlets - Li Hua Zhang; Hong Bo Shao; Gong Fu Ye; Yi Ming Lin (Acta Physiologiae Plantarum, 2012)

Anomalous temperature–growth response of Abies faxoniana to sustained freezing stress along elevational gradients in China’s Western Sichuan Province - Zong Shan Li; Guo Hua Liu; Bo Jie Fu; Chan Juan Hu; Shu Zheng Luo; Xing Liang Liu; Fei He (Trees, 2012)

Differential effects of paraoxonase 1 (PON1) polymorphisms on cancer risk: evidence from 25 published studies - Dai-Hua Fang; Cong-Hai Fan; Qiang Ji; Bo-Xiang Qi; Juan Li; Lu Wang (Molecular Biology Reports, 2012)

Genetic characterization of subtype H1 avian influenza viruses isolated from live poultry markets in Zhejiang Province, China, in 2011 - Hai-bo Wu; Chao-tan Guo; Ru-feng Lu; Li-hua Xu; En-kang Wo; Jin-biao You; Yi-ting Wang; Qiao-gang Wang; Nan-ping Wu (Virus Genes, 2012)

Characterization of a highly pathogenic H5N1 avian influenza virus isolated from ducks in Eastern China in 2011 - Wu Hai-bo; Guo Chao-tan; Lu Ru-feng; Xu Li-hua; Wo En-kang; You Jin-biao; Wang Yi-ting; Wang Qiao-gang; Wu Nan-ping (Archives of Virology, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Dissection of genetic overlap of drought and low-temperature tolerance QTLs at the germination stage using backcross introgression lines in soybean - Wen Bo Zhang; Peng Cheng Qiu; Hong Wei Jiang; Chun Yan Liu; Da Wei Xin; Can Dong Li; Guo Hua Hu; Qing Shan Chen (Molecular Biology Reports, 2012)

Dynamics and functions of CD4+CD25high regulatory T lymphocytes in Chinese rhesus macaques during the early stage of infection with SIVmac239 - Shao-You Li; Hou-Jun Xia; Zheng-Xi Dai; Gao-Hong Zhang; Bo Fan; Ming-Hua Li; Rui-Rui Wang; Yong-Tang Zheng (Archives of Virology, 2012)

Characterization of Prototheca zopfii Associated with Outbreak of Bovine Clinical Mastitis in Herd of Beijing, China - Jian Gao; Han-qi Zhang; Jian-zhong He; Yang-hua He; Shu-mei Li; Rong-guang Hou; Qiao-xing Wu; Yang Gao; Bo Han (Mycopathologia, 2012)

H. pylori related proinflammatory cytokines contribute to the induction of miR-146a in human gastric epithelial cells - Na Li; Xiang Xu; Bin Xiao; En-Dong Zhu; Bo-sheng Li; Zhen Liu; Bin Tang; Quan-Ming Zou; Hua-Ping Liang; Xu-Hu Mao (Molecular Biology Reports, 2012)

Molecular characterization of three heat shock protein 70 genes and their expression profiles under thermal stress in the citrus red mite - Li-Hong Yang; Hong-Bo Jiang; Yong-Hua Liu; Wei Dou; Jin-Jun Wang (Molecular Biology Reports, 2012)

CREB-binding protein silencing inhibits thrombin-induced endothelial progenitor cells angiogenesis - Hong Jiang; Si-si Chen; Jian Yang; Jing Chen; Bo He; Li-hua Zhu; Lang Wang (Molecular Biology Reports, 2012)

Large-scale sequencing of normalized full-length cDNA library of soybean seed at different developmental stages and analysis of the gene expression profiles based on ESTs - Ai-Hua Sha; Chen Li; Xiao-Hong Yan; Zhi-Hui Shan; Xin-An Zhou; Mu-Lan Jiang; Han Mao; Bo Chen; Xia Wan; Wen-Hui Wei (Molecular Biology Reports, 2012)

Glutamate carboxypeptidase II gene polymorphisms and neural tube defects in a high-risk Chinese population - Hua Xie; Jin Guo; Jianhua Wang; Fang Wang; Huizhi Zhao; Chi Liu; Li Wang; Xiaolin Lu; Lihua Wu; Yihua Bao; Jizhen Zou; Ting Zhang; et al. (Metabolic Brain Disease, 2012)

Temperature reconstruction from tree-ring maximum latewood density of Qinghai spruce in middle Hexi Corridor, China - Feng Chen; Yu-jiang Yuan; Wen-shou Wei; Shu-long Yu; Zi-ang Fan; Rui-bo Zhang; Tong-wen Zhang; Qin Li; Hua-ming Shang (Theoretical and Applied Climatology, 2012)

Bisphenol A exposure modifies methylation of imprinted genes in mouse oocytes via the estrogen receptor signaling pathway - Hu-He Chao; Xi-Feng Zhang; Bo Chen; Bo Pan; Lian-Jun Zhang; Lan Li; Xiao-Feng Sun; Qing-Hua Shi; Wei Shen (Histochemistry and Cell Biology, 2012)

G6PD Genotype and Its Associated Enzymatic Activity in a Chinese Population - Wei Ying Jiang; Bing Yi Zhou; Guo Long Yu; Han Liu; Jing Bo Zeng; Qun Di Lin; Hong Li Xi; Hua Liang (Biochemical Genetics, 2012)

Ginsenoside-Rd potentiates apoptosis induced by hydrogen peroxide in basilar artery smooth muscle cells through the mitochondrial pathway - Shi-Yang Li; Xiao-Guang Wang; Ming-Ming Ma; Yun Liu; Yan-Hua Du; Xiao-Fei Lv; Jia-Guo Zhou; Yong-Bo Tang; Yong-Yuan Guan (Apoptosis, 2012)

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)

The Potential Influence of Seasonal Climate Variables on the Net Primary Production of Forests in Eastern China - Zong Shan Li; Guo Hua Liu; Bo Jie Fu; Jin Long Zhang (Environmental Management, 2011)

TP53 codon 72 polymorphism and colorectal cancer susceptibility: a meta-analysis - Jing-Jun Wang; Yuan Zheng; Liang Sun; Li Wang; Peng-Bo Yu; Jian-Hua Dong; Lei Zhang; Jing Xu; Wei Shi; Yu-Chun Ren (Molecular Biology Reports, 2011)

PI3K/Akt signaling pathway is involved in the pathogenesis of ulcerative colitis - Xiao Li Huang; Jin Xu; Xiao Hui Zhang; Bo Yun Qiu; Lan Peng; Meng Zhang; Hua Tian Gan (Inflammation Research, 2011)

Synthesis of benzo[b][1,4]oxazin-3(4H)-ones via smiles rearrangement for antimicrobial activity - Liang Fang; Hua Zuo; Zhu-Bo Li; Xiao-Yan He; Li-Ying Wang; Xiao Tian; Bao-Xiang Zhao; Jun-Ying Miao; Dong-Soo Shin (Medicinal Chemistry Research, 2011)

Naturalization of alien plants in China - Hua Jiang; Qiang Fan; Jin-Tian Li; Shi Shi; Shao-Peng Li; Wen-Bo Liao; Wen-Sheng Shu (Biodiversity and Conservation, 2011)

Effects of palmitic acid on lipid metabolism homeostasis and apoptosis in goose primary hepatocytes - Zhixiong Pan; Jiwen Wang; Hui Tang; Liang Li; Jia Lv; Lu Xia; Chunchun Han; Feng Xu; Hua He; Hengyong Xu; Bo Kang (Molecular and Cellular Biochemistry, 2011)

Polyclonal rabbit anti-murine plasmacytoma cell globulins induce myeloma cells apoptosis and inhibit tumour growth in mice - Bo Mu; Jin-liang Yang; Lan-tu Gou; Yu-qin Yao; Yan Zhou; Zhi-hui Cheng; Hua-shan Shi; Zhi-yong Li; Yuan Wen; Fei Leng; Feng-yu Cui; Tian-tai Ma; et al. (Apoptosis, 2011)

Efficacy and safety of escitalopram versus citalopram in major depressive disorder: a 6-week, multicenter, randomized, double-blind, flexible-dose study - Jian-Jun Ou; Guang-Lei Xun; Ren-Rong Wu; Le-Hua Li; Mao-Sheng Fang; Hong-Geng Zhang; Shi-Ping Xie; Jian-Guo Shi; Bo Du; Xue-Qin Yuan; Jing-Ping Zhao (Psychopharmacology, 2011)

Analysis of correlation between blood biochemical indicators and bone mineral density of post-menopausal women - Shun-zhi Liu; Li-fang Tian; Peng Xu; Gui-hua Zhuang; Fang Zheng; Juan Tian; Qi-Lan Ning; Bo-Feng Zhu; She-Min Lu; Hong Yan (Molecular Biology Reports, 2011)

Synthesis and in vitro antimicrobial activity of benzo[b][1,4]thiazin-3(4H)-ones via smiles rearrangement - Hao Yang; Liang Fang; Zhu-Bo Li; Fang-Kui Ren; Li-Ying Wang; Xiao Tian; Dong-Soo Shin; Hua Zuo (Medicinal Chemistry Research, 2011)

Use of the pyrG gene as a food-grade selection marker in Monascus - Bo-hua Wang; Yang Xu; Yan-ping Li (Biotechnology Letters, 2010)

Structural basis for the decrease in the outward potassium channel current induced by lanthanum - Li Hong Wang; Na Jiang; Bo Zhao; Xiao Dong Li; Tian Hong Lu; Xiao Lan Ding; Xiao Hua Huang (JBIC Journal of Biological Inorganic Chemistry, 2010)

Population variation of invasive Spartina alterniflora can differentiate bacterial diversity in its rhizosphere - Ming Nie; Le Xuan Gao; Jun Hong Yan; Xiao Hua Fu; Ming Xiao; Ji Yang; Bo Li (Plant Ecology, 2010)

Development of real-time and nested RT-PCR to detect astrovirus and one-year survey of astrovirus in Jiangmen City, China - Ying-chun Dai; Qiao-hua Xu; Xian-bo Wu; Gui-fang Hu; Ya-li Tang; Jian-dong Li; Qing Chen; Jun Nie (Archives of Virology, 2010)

Cytogenetic analysis of reciprocal hybrids and their parents between Larix leptolepis and Larix gmelinii: implications for identifying hybrids - Shou Gong Zhang; Wen Hua Yang; Su Ying Han; Bo Tao Han; Mao Xue Li; Li Wang Qi (Tree Genetics & Genomes, 2010)

Characterization of a Moniezia expansa ubiquitin-conjugating enzyme E2 cDNA - Hui Zhang; Wen-juan Zhao; Li-chao Kang; Xin-hua Wang; Xin-wen Bo (Molecular Biology Reports, 2010)

The effects of CYP2C9 and CYP2C19 genetic polymorphisms on the pharmacokinetics and pharmacodynamics of glipizide in Chinese subjects - Bo Tan; Yi-Fan Zhang; Xiao-Yan Chen; Xiao-Hua Zhao; Guo-Xin Li; Da-Fang Zhong (European Journal of Clinical Pharmacology, 2010)

Effects of Selenium on the Antioxidant Enzymes Response of Neocaridina heteropoda Exposed to Ambient Nitrite - Hong-wei Wang; Hai-ming Xu; Guo-hua Xiao; Chun-long Zhao; Zi-hui Wang; Duan-bo Cai; Hong-quan Li; Jian-hua Zhao (Bulletin of Environmental Contamination and Toxicology, 2010)

Correlation Analysis Between Bone Mineral Density and Serum Element Contents of Postmenopausal Women in Xi’an Urban Area - Shun-Zhi Liu; Hong Yan; Peng Xu; Jian-Ping Li; Gui-Hua Zhuang; Bo-Feng Zhu; She-Min Lu (Biological Trace Element Research, 2009)

Evidence for programmed cell death and activation of specific caspase-like enzymes in the tomato fruit heat stress response - Gui-Qin Qu; Xiang Liu; Ya-Li Zhang; Dan Yao; Qiu-Min Ma; Ming-Yu Yang; Wen-Hua Zhu; Shi Yu; Yun-Bo Luo (Planta, 2009)

TRANSPARENT TESTA 12 genes from Brassica napus and parental species: cloning, evolution, and differential involvement in yellow seed trait - You-Rong Chai; Bo Lei; Hua-Lei Huang; Jia-Na Li; Jia-Ming Yin; Zhang-Lin Tang; Rui Wang; Li Chen (Molecular Genetics and Genomics, 2009)

Effects of RNA interference-induced tryptase down-regulation in P815 cells on IL-6 and TNF-α release of endothelial cells - Yi-feng Jiang; Feng-di Zhao; Xiao-bo Li; Yan-xia Ning; Xiu-ling Zhi; Rui-zhe Qian; Lian-hua Yin (Journal of Zhejiang University-SCIENCE B, 2008)

Microsatellite Analysis of Genetic Variation and Population Genetic Differentiation in Autotetraploid and Diploid Rice - Li Luan; Xing Wang; Wen-Bo Long; Yu-Hua Liu; Sheng-Bin Tu; Zhan-Peng Zhao; Fan-Lun Kong; Mao-Qun Yu (Biochemical Genetics, 2008)

Molecular characterization and phylogenetic analysis of membrane protein genes of porcine epidemic diarrhea virus isolates in China - Jian-Fei Chen; Dong-Bo Sun; Cheng-Bao Wang; Hong-Yan Shi; Xiao-Chen Cui; Sheng-Wang Liu; Hua-Ji Qiu; Li Feng (Virus Genes, 2008)

Notch activation promotes cell proliferation and the formation of neural stem cell-like colonies in human glioma cells - Xue-Ping Zhang; Gang Zheng; Lian Zou; Hui-Ling Liu; Li-Hong Hou; Peng Zhou; Dan-Dan Yin; Qi-Jun Zheng; Liang Liang; Su-Zhen Zhang; Lei Feng; Li-Bo Yao; et al. (Molecular and Cellular Biochemistry, 2007)

BRD2 is one of BRD7-interacting proteins and its over-expression could initiate apoptosis - Ming Zhou; Xiao-Jie Xu; Hou-De Zhou; Hua-Ying Liu; Jia-Jin He; Xiao-Ling Li; Cong Peng; Wei Xiong; Song-Qing Fan; Jian-Hong Lu; Jue Ouyang; Shou-Rong Shen; et al. (Molecular and Cellular Biochemistry, 2006)

Improved production of pristinamycin coupled with an adsorbent resin in fermentation by Streptomyces pristinaespiralis - Bo Jia; Zhi-Hua Jin; Yin-Lin Lei; Le-He Mei; Ning-Hui Li (Biotechnology Letters, 2006)

Molecular analysis of early rice stamen development using organ-specific gene expression profiling - Xiao-Chun Lu; Hua-Qin Gong; Mo-Li Huang; Su-Lan Bai; Yang-Bo He; Xizeng Mao; Zhi Geng; Song-Gang Li; Liping Wei; Jie-Shuai Yuwen; Zhi-Hong Xu; Shu-Nong Bai (Plant Molecular Biology, 2006)

Changes in Soil Microbial Community Associated with Invasion of the Exotic Weed, Mikania micrantha H.B.K - Wei-hua Li; Cong-bang Zhang; Hong-bo Jiang; Guo-rong Xin; Zhong-yi Yang (Plant and Soil, 2006)

Frame design of remote sensing monitoring for volcanic activities in Changbai mountains - Li-qun Bo; Yun-ping Zhao; Ren-kui Hua (Chinese Geographical Science, 2003)

Research on disturbed mechanism of thermal noises of the surface in abrupt geothermal anomaly - Li-qun Bo; Xin-liang Xu; Ren-kui Hua; Xue-xia Zhang (Chinese Geographical Science, 2001)